Psychrotrophic bacteria in dairy chain across some Egyptian governorates: Prevalence, biofilm formation, proteolytic activity, and antibiotic resistance - Eman A. Nafei; Dina A.B. Awad (Food and Humanity, 2026)

Paleomagnetic calibration, mineralogy, provenance, and diagenetic controls on Upper Paleozoic siliciclastic successions: Implications for chronostratigraphy, basin evolution, and reservoir quality on the northern Gondwana margin - Haitham M. Ayyad; Mohamed W. Abd El-Moghny; Mohamed H. Helal; Ashraf M. Al-Nashar; Nabil A. Abdel Hafez; Ahmed Awad; Sherif Farouk; Mohamed Fathy (Journal of African Earth Sciences, 2026)

Multifaceted nature of milk: potential source of parasites and a natural approach to parasite infection control - Dina A. B. Awad; Safaa A. Bayoumi; Ahmed Hamad (Veterinary Research Communications, 2026)

Application of in vitro digestion and dialysability procedure for bioavailability evaluation of toxic elements in green leafy vegetables: a realistic health risk assessment by Monte Carlo simulation - Maha Abdallah Alnuwaiser; Hala Hazam Al-Otaibi; Refaat A. Eid; Shaban Ragab Ibrahim Sukkar; Nibal T. Al-Dalgamony; A. Al Solami; Ishraga Galal Eldin Abdalla Awad (Food Additives & Contaminants: Part A, 2026)

Systems pharmacology, structural modeling, and experimental validation reveal retinoic acid as a modulator of immune-fibrotic networks in chronic kidney disease - Ayman E. Abdelaziz; Ahmed A. Shokeir; Basem I. Awad; Omali Y. El-Khawaga (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

In Vitro and In Silico Investigations of the Acaricidal Activity of Carvacrol Against Rhipicephalus annulatus - Samar M. Ibrahium; Abdel-Azeem S. Abdel-Baki; Fatma I. Abo El-Ela; Aliaa A. Balegh; Ahmed A. Wahba; Saleh Al-Quraishy; Ezzat M. Awad; Manal Ahmed; Wafaa G. Mahmoud; Shawky M. Aboelhadid (Acta Parasitologica, 2026)

Paclobutrazol-mediated improvement of brown spot resistance in rice seedlings under salinity stress conditions - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Abdelaziz M. Tahoon; Hosny Hamed Kesba; Elsayed Abd Elmaksoud Abomarzoka; Ahmed Mahmoud Ismail; Awad Mohamed El-Sayed; Wael Elmenofy; Metwaly Mahfouz Salem Metwaly (European Journal of Plant Pathology, 2026)

Endophytic fungi: A potential source of bioactive compounds - Sherien M.M. Atalla; Aliaa R El Shamy; Wesam M Hussein; Ruba A. Ashy; Rawabi Zahed; Hassan M Awad (South African Journal of Botany, 2026)

Enhancing tomato plant immune responses through microbial bio-inducers against Pythium irregular root rot - Mohamed S. Attia; Mohamed M. Nofel; Amer M. Abdelaziz; Eslam K. Kandil; Abdulrahman E. Singer; Youssef E. Madkour; Mohammed G. Awad; Muostafa M. Abdelsamad; Abdullah A. Mahmoud; Hassan A. Rudayni; Amr Elkelish; Gharieb S. El-Sayyad (Physiological and Molecular Plant Pathology, 2026)

Glutaraldehyde and formalin impact the performance, expression of immune- growth- antioxidant-related genes, and DNA integrity of Nile tilapia (Oreochromis niloticus) - Awad A. Abdelbaky; Magdy Mahfouz; Enas A. Kasem; Ahmed H. Sherif (Regional Studies in Marine Science, 2026)

Innovative synbiotic functional fermented barley-based milk using novel isolated probiotic Levilactobacillus brevis HBE2 and Enterococcus faecalis HBE4 - Hany Elkashef; Nesren Elsayed; Awad A. Awad; Ashwak Abdel Moneim Hassan (Innovative Food Science & Emerging Technologies, 2026)

Comparative in vitro and in vivo acaricidal activity of D-limonene against Argas persicus with biochemical and ultrastructural insights - Asmaa A. Hassan; Shawky M. Aboelhadid; Asmaa A. Kamel; Waleed M. Arafa; Abdel-Azeem S. Abdel-Baki; Khaled M. Shokier; Saleh Al-Quraishy; Ezzat M. Awad; Shams G. Abd El-Kareem; Sahar M. Gadelhaq (Biocatalysis and Agricultural Biotechnology, 2026)

Genetic Diversity Analysis Using Start Codon Targeted (SCoT) and Sequence-Related Amplified Polymorphism (SRAP) Markers and Some Leaf Anatomical Traits in Sixteen Rutaceae Taxa - Mohamed A. Abdein; Samah O. Osman; Amr M. M. Mahmoud; Sahar A. M. Shamseldin; Mai M. Wahba; Sayed Y. Mohamed; Emadeldin A. H. Ahmed; Salwa El-Habashy; Rania A. E. Abdelzaher; Noha A. Sukar; Amany M. Mousa; Amal Ahmed Alyamani; et al. (Plant Molecular Biology Reporter, 2026)

Efficacy and safety of Ongericimab in patients with hypercholesterolemia: a systematic review and meta-analysis - Ahmed L. Youseif; Ahmed F Younis; Ziad W. Elmezayen; Mohamed Eldahrawy; Noha Hammad; Belal Mohamed Hamed; Amr Reda Saleh; Alaa Ashraf Mohamed; Omar Abdulrahman Saad; Aya M. Ramadan; Abdelaziz A. Awad (European Journal of Clinical Pharmacology, 2026)

Eco-friendly suppression of date palm (Phoenix dactylifera L.) Fusarium wilt using Streptomyces biocontrol agents from the rhizosphere - Mohamed A. Awad; Adel D. Al-Qurashi; Kamal A. M Abo-Elyousr (Journal of Plant Pathology, 2026)

Natural radioactivity distribution and environmental risk assessment of Upper Cretaceous-Lower Paleogene sedimentary successions of Wadi Queih area, Red Sea, Egypt - Alanoud A. Atia; Awad A. Omran; Ahmed R. M. El Younsy; Nageh A. Obaidalla; Abdelhamid M. Salman; Ghada Salaheldin (Environmental Monitoring and Assessment, 2026)

Selenium-Astaxanthin Co-Supplementation Synergistically Reduces PCSK9 Expression, Upregulates LDL Receptors, and Improves lipid profile and Cardiovascular Markers in Menopausal Ovariectomized Rats by attenuating inflammation and lipid peroxidation - Heyam Faisal Zaer; Dalia Zaal Albalawi; Alhanouf S. Alkhuraisi; Fai Faisal Awad; Hebatallah Husseini Atteia; Hoda A. Salem; Salwa Fares Ahmed (Biological Trace Element Research, 2026)

Empagliflozin as a potential therapy for PCOS: Restoring hormonal balance and ovarian function in a letrozole-induced rat model - Heba A. Habib; Mahmoud El-Daly; Yahya I. Asiri; Saud Alqahtani; Eman M. Awad; Sara MN. Abdel Hafez; Al-Shaimaa F. Ahmed; Aliaa F. Anter (Tissue and Cell, 2026)

Bioactive-driven modulation of structural, rheological, and functional properties in tiger nut–based frozen food matrices enriched with selected fruit pulps - Hesham A. Ismail; Wafaa M. Salama; Arwa M. Ali; Wael F. Elkot; Tawfiq Alsulami; Suleiman A. Althawab; Basim M. Alohali; Ammar Al-Farga; Rezk A. Awad (Food Research International, 2026)

Green air-assisted LLME using a novel hydrophobic deep eutectic solvent for the extraction and quantification of Brilliant Green and Rhodamine B in food matrices - Ahmed A. Fouda; A.B. Abdallah; Fathi S. Awad (Food Chemistry, 2026)

Formulation and Characterization of Niosomal Suspension of Aloenin for the Treatment of Myocardial Toxicity in Isoproterenol-Induced Rats Via Alteration HO-1/Nrf2/TLR4/ Caspase-3 Signaling Pathways - Samiyah Alshehri; Misbahuddin Rafeeq; Muhammad Afzal; Alaa Hamed Habib; Hadeel A Alsufyani; Samy A Abusikkien; Sami I. Alzarea; Omar Awad Alsaidan; Nadeem Sayyed; Imran Kazmi (Journal of Pharmaceutical Innovation, 2026)

Modulation of arsenic uptake and detoxification in maize (Zea mays L.) by plant-based iron oxide nanoparticles - Tauseef Anwar; Huma Qureshi; Muhammad Imran; Hossam S. El-Beltagi; Salohiddinjon Yunusov; Shuqurillo Ziyadov; Muydinjon M. Muminov; Gamal Awad El-Shaboury; Dilbar Bazarbayeva; Ibtisam M. Alsudays; Khalid H. Alamer; Munisa Bekmukhamedova; et al. (Biodegradation, 2026)

Therapeutic Impact of Plant-Derived Extracts and their Silver Nanoparticle-Loaded Extracts on the Zoonotic Parasite Hymenolepis Nana Infection - Wesam M. A. Elgendy; Hany M. El-Wahsh; Doaa Naguib; Rasha A. Elmahy; Suzan Awad AbdelGhany Morsy; Ashraf Fawzy Mosa Ahmed; Marim Fayz Abdow; Nabeel Hussain Alhussainy; Faten Abdullah Al Braikan; Ahmed Bendari; Akram Abu-Okail; Amira Mohamed AbdelHady Elhosyni (Acta Parasitologica, 2026)

Effects of a Magnetic Field on Surface and Subsurface Drip Irrigation Water, Tomato Plants and Desert Sandy Soil Characteristics - Ahmed A. Al‐Othman; Doaa M. El‐Shinawy; Awad Ali Tayoush Oraiath; Abdallah Elshawadfy Elwakeel; Ahmed Z. Dewidar; Ahmed Elbeltagi; A. H. Hamza (Irrigation and Drainage, 2026)
This study, conducted in Shosha, Minia, Egypt, aimed to evaluate the effects of magnetically treated saline groundwater on both soil characteristics and the performance of tomato crops grown in arid sandy soils. The influence of magnetic fields on water quality was first assessed to determine its suitability for irrigation. Subsequently, the combined effects of MWT with different irrigation methods—namely, surface drip irrigation (SDI) and subsurface drip irrigation (SSDI)—as well as system design types (closed vs. open systems), were examined to understand their impact on soil health and chemical properties under saline conditions. Magnetic treatment significantly improved water quality by reducing sodium and chloride accumulation in the root zone and decreasing the Na/Cl ratio from 1.07 to 0.98. This facilitated salt leaching and reduced plant salt stress. Treated water also lowered soil electrical conductivity (EC) and soluble ion concentrations while increasing soil moisture retention and field capacity. SSDI with magnetised water achieved a wetted soil volume of 94,500 cm 3 —vastly greater than 6720 cm 3 under unmagnetised open SDI. Emitter clogging ratio (ECR) was reduced from 12% to 5%, improving system reliability. Application efficiency rose from 89% to 97%, and emission uniformity improved from 90% to 96%.

Isolation, Identification, and Pathogenicity of Entomopathogenic Fungal Strains and Their Secondary Metabolites Against Spodoptera frugiperda (Lepidoptera: Noctuidae) - Fatmaalzahraa A. Senousy; El Arnaouty S.A; Mona N. Kortam; Ismail M. Ismail; Mona Awad; Marwa A. Zayton (Neotropical Entomology, 2026)
The fall aِrmyworm, Spodoptera frugiperda (J.E. Smith), causes significant yield losses due to its high fecundity, broad host range, defoliation capability, and voracious larval feeding. Biological control using microorganisms has gained attention as a sustainable alternative to chemical pest management. Entomopathogenic fungi employ distinct modes of action and produce secondary metabolites with insecticidal properties. This study aimed to isolate and identify indigenous entomopathogenic fungal species and evaluate their pathogenicity against S. frugiperda . Three isolates belonging to the division Ascomycota were recovered from soil samples and identified as Botryotrichum domesticum isolate MP3H-5, Albifimbria verrucaria isolate E16, and Purpureocillium lilacinum isolate WARSO2 6 8. When applied at a concentration of 1 × 10 9 conidia mL⁻ 1 , the fungal isolates induced significant cumulative mortality (60 to 84.44%) in S. frugiperda larvae at 14 days post-treatment. Albifimbria verrucaria was the most virulent, exhibiting the lowest LC 50 (2 × 10 7 conidia mL⁻ 1 ) and LT 50 (0.46 days). At a lower concentration of 1 × 10 7 conidia mL⁻ 1 , the P. lilacinum isolate caused the highest pupal mortality (80%) at 7 days post-treatment. Crude fungal metabolites also demonstrated larvicidal activity, resulting in cumulative mortality rates of up to 50%. Furthermore, larvae treated with the entomopathogenic fungi showed elevated catalase activity. The high toxicity observed is likely associated with fungal secondary metabolites, which were characterized using GC-MS analysis. Under laboratory conditions, the tested entomopathogenic fungal isolates demonstrated strong potential as microbial agents for the control of S. frugiperda . However, further field-based validation is necessary to confirm their efficacy.

Lectin Gene Families in Three Phaseolus Species: Genome-Wide Identification, Evolutionary Analysis, Pleiotropic Effect, and Regulation Under Multiple Stress Conditions - Makarim Elfadil M. Osman; Amina I. Dirar; Mohanad A. Ibrahim; Rieham Sallah H. Osman; Doaa Awad Yassin Ali; Somia Elmosharaf Elrayah Yousif; Hana Badreldin Mohamed Abakar; Nada Hassan M. Haj; Emadeldin Hassan E. Konozy (Journal of Molecular Evolution, 2026)

Alteplase versus tenecteplase in acute ischemic stroke with large vessel occlusion: a systematic review and meta-analysis - Mostafa Hossam El Din Moawad; Ibrahim Serag; Ahmed A. Abo Elnaga; Dina Essam Abo-elnour; Hamza A. Abdul-Hafez; Mohamed Ahmed Hammad; Lobna Ahmed Mohamed; Rawan Kamal Mohamed; Amir N. Attia; Abdelaziz A. Awad; Ibraheem M. Alkhawaldeh; Mahmoud Hegazy; et al. (European Journal of Clinical Pharmacology, 2026)

Distributed control and optimization in building energy systems: a technical survey of multi-agent architectures and algorithms - Ahmed N. Abdalla; Rendong Ji; Omar I. Awad; Ancheng Wang; Yongfeng Tang; Yao Liu; Mahdi A. Mahdi (Energy and Buildings, 2026)

A flexible photothermal device based on silver nanoparticle-integrated cellulose matrix for interfacial solar steam generation: Rethink waste and reinvigorate water - Mina Shawky Adly; Salma M. Abo Kamar; Mohamed Noufal; Soheir A. EL-Hakam; Awad I. Ahmed; Amr Awad Ibrahim (Desalination, 2026)

Development of Functional Dairy Byproducts-based Beverages Using Rutab Date and Probiotic Apilactobacillus Kunkeei EABW06 - Hany Elkashef; Awad A. Awad; Ashwak Abdel Moneim Hassan (Probiotics and Antimicrobial Proteins, 2026)
This study was designed to valorize dairy byproducts including cheese whey and buttermilk through developing fermented beverages using a novel isolated Apilactobacillus kunkeei EABW06 strain from Egyptian bee’s wax. Cheese whey or buttermilk was fermented with A. kunkeei and compared to fermented whey or buttermilk supplemented with Rutab date pulp on day one or after 15 days of cold storage. Physicochemical, microbiological, sensory, proteolytic, and various functional properties were investigated. Fermented buttermilk beverages particularly supplemented with date pulp had the highest viscosity and water-holding capacity at the beginning or after 15 days of cold storage. The supplementation with date pulp led to increase the viable count of A. kunkeei . Compared to fermented whey beverages, fermented buttermilk beverages recorded the greatest scores of sensory attributes. The proteolytic, ACE-I, and antioxidant activity enhanced in fermented buttermilk supplemented with or without date pulp. A storage period exhibited a positive effect on the proteolysis, ACE-I, and DPPH radical scavenging properties of fermented beverages. All fermented beverages showed a great inhibitory impact against the growth of various species of fungi and bacteria. Fermented buttermilk beverages demonstrated the highest cytotoxicity against Caco2 cell lines with IC 50 values of 81.22–86.89 μg/mL. However, fermented whey beverages had the strongest inhibition of α-amylase and α-glucosidase enzymes. These findings propose that whey or buttermilk serves as an effective medium for the growth of A. kunkeei and potentially enabling the development of innovative fermented dairy beverages with beneficial health effects.

A comprehensive systematic review of randomized controlled trials on anesthetic agents in children’s upper gastrointestinal endoscopy: highlighting safety concerns and efficacy - Amr Elrosasy; Mahmoud Diaa Hindawi; Mohamed Abo Zeid; Abdelaziz A. Awad; Ahmed W. Abbas; Mohammad Al Diab Al Azzawi; Eslam Afifi; Ahmed Amgad; Mohamed Yasser; Khalid Sarhan; Sara Chikh Aissa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Upper gastrointestinal endoscopy (GIE) is essential for diagnosing and treating gastrointestinal disorders in children aged 6–12 years, yet it often requires sedation due to the significant discomfort and pain involved. We conducted a PRISMA 2020–compliant systematic review of randomized controlled trials (RCTs) from PubMed, Web of Science, Scopus, and Ovid (inception to March 30, 2024). Inclusion criteria are as follows: RCTs comparing sedative regimens (e.g., propofol, ketamine, remimazolam, dexmedetomidine) in children undergoing upper GIE. Exclusion criteria are as follows: non-RCTs, studies outside the age range, or non-English publications. Risk of bias was assessed using Cochrane ROB-2. Data were extracted for recovery time, hemodynamic parameters, and adverse events (hypoxia, bradycardia, dizziness). A systematic synthesis of outcomes was performed, with results presented descriptively and quantitatively (e.g., event rates, mean differences) to compare regimens. Nineteen RCTs were included with a total of 1955 patients. Propofol, either alone or in combination, was frequently used. The propofol-ketamine combination showed better hemodynamic stability (92.2 ± 16.8 bpm) compared to propofol-fentanyl (76.8 ± 13.8 bpm). S-ketamine demonstrated dose-dependent effects—0.3 mg/kg provided the shortest recovery time (33.5 min) with moderate dizziness (40.0%)—while 0.5 mg/kg offered optimal heart rate maintenance (93.81 bpm) but longer recovery (35.67 min) and increased dizziness (43.3%). The 0.7 mg/kg dose showed faster recovery than 0.5 mg/kg (33.5 vs 35.67 min), but the highest dizziness rates (73.3%). Post-procedural complications were minimal except for dose-dependent neurological effects with S-ketamine (visual disturbances peaking at 27.6% with 0.3 mg/kg). Remimazolam showed the fastest recovery overall. Adverse events varied by regimen: propofol-ketamine had higher hypoxia (6.8%) and dizziness (34.1%), while propofol-fentanyl showed more bradycardia (24.4%). Overall, remimazolam and dexmedetomidine regimens were linked to fewer complications, though they required careful monitoring for hypotension. However, heterogeneity in outcomes (e.g., recovery times, adverse events) underscores the need for individualized regimen selection. Limitations include variability in study designs and insufficient data on minimal effective doses. Further RCTs should standardize outcome measures and optimize dosing for children undergoing endoscopy.

Petrogenesis of Fe-Ti-(P) oxide bearing layered gabbroic intrusion in the Northern Eastern Desert of Egypt: insights into parent melt composition and genesis of oxide ores - Amr El-Awady; Doaa A. Abdelnaiem; Sherif Kharbish; Hamdy A. Awad; Mustafa Kumral; Mustafa Kaya; Amr Abdelnasser (Journal of African Earth Sciences, 2025)

A consortium of Aspergillus species biodegrades polypropylene plastic - Asma Mudhahi Alshammari; Promy Virk; Rasha Elsayim; Norah Raqi Al-Otaibi; Alanoud Tariq Al Sudairi; Manal A. Awad; Abdel-Basit Al-Odayni; Dalia Fouad (Environmental Pollution, 2025)

miRNAs and their multifaceted role in cutaneous wound healing - Reda M. Mansour; Sherif S. Abdel Mageed; Farah A. Awad; Mohamed M. Sadek; Shehab Ahmed Adel; Alaa Ashraf; Khaled M. Alam-Eldein; Nada E. Ahmed; Rana Y. Abdelaziz; Esraa Farid Tolba; Hend H. Mohamed; Nehal I. Rizk; et al. (Functional & Integrative Genomics, 2025)

From fatty liver to fibrosis: the impact of miRNAs on NAFLD and NASH - Reda M. Mansour; Sherif S. Abdel Mageed; Ahmed I. Abulsoud; Ghadir A Sayed; Radwa H. Lutfy; Farah A. Awad; Mohamed M. Sadek; Abanoub A. S. Shaker; Osama A. Mohammed; Mustafa Ahmed Abdel-Reheim; Hanan Elimam; Ahmed S. Doghish (Functional & Integrative Genomics, 2025)

Sustainable Water Management of Drip‐Irrigated Green Beans: Evaluation of Yield, Irrigation Water Productivity, Soil Moisture and Salinity Dynamics in the Soil by the SALTMED Model Under Organic Soil Mulching and Water Stress - Amal E. Awad; Mohamed E. Abuarab; R. E. Abdelraouf; Gomaa A. Bakeer; Mohamed Abdel‐Hady; Mohamed A. El‐Shawadfy (Irrigation and Drainage, 2025)
This study examined how organic mulching and deficit irrigation affect soil moisture and salinity in sandy soils, comparing field data with the SALTMED model outputs. The field experiment featured four irrigation treatments—100% IRg, 75% IRg, 50% IRg and 50% IRg with partial root drying (PRD)—and four mulching treatments: uncovered soil (UC), plastic mulch (PM), rice straw mulch (RSM) and compacted rice straw mulch (CRSM) over the 2022 and 2023 seasons. In 2022, the 50% IRg–PRD with CRSM yielded the highest at 8611 kg ha −1 , while the 50% IRg with UC had the lowest at 6009 kg ha −1 . The highest irrigation water productivity (IWP) was 5.56 kg m −3 under the 50% IRg–PRD and CRSM treatment, and the lowest was 2.45 kg m −3 with 100% IRg and UC. The SALTMED model accurately simulated crop yields with R 2 values of 0.982 and 0.949 across all treatments and high R 2 values of 0.996 and 0.992 for observed versus simulated IWPs. The model showed significant sensitivity in simulating soil moisture and salinity changes across treatments.

Exploring the Polyphenolic Content and Pharmacological Potential of Cauliflower Leaf Extract: A Combined Experimental and Computational Approach - Salma A. El-Sawi; Maii A.I. Maamoun; Ayman A. Farghaly; Ghada E.A. Awad (South African Journal of Botany, 2025)

Combined efficacy of Bacillus amyloliquefaciens CIM95 and melatonin in reducing anthracnose in strawberries (Fragaria × ananassa Duch.) by enhancing antioxidant activity and defense-related genes - Anam Moosa; Arwa Abdulkreem AL-Huqail; Dikhnah Alshehri; Suliman Mohammed Suliman Alghanem; Faisal Zulfiqar; Gamal Awad El-Shaboury; Fahad Al-Asmari; Nurah M. Alzamel; Layla A. Alahmari; Tolga İzgü (International Journal of Food Microbiology, 2025)

Antifungal and anti-toxigenic activities of Origanum onites and Thymus capitatus essential oils and ethanolic extracts against mycotoxigenic fungi isolated from barley - Islem Dammak; Zohra Hamdi; Myriam Lamine; Haifa Hajri; Shereen Basiouni; Spyridon Ntougias; George Tsiamis; Mete Yilmaz; Fatma Acheuk; Mevlut Emekci; Wolfgang Eisenreich; Claudia Huber; et al. (Food Chemistry, 2025)

Increased plasma concentrations of 6-oxo-methylphenidate in CES1 G134E carriers following a single oral dose of methylphenidate - Qingchen Zhang; Philip W. Melchert; Ahmed Awad; Christopher R. McCurdy; Beth Krone; Jeffrey Newcorn; Tanya E. Froehlich; Mark A. Stein; Josephine Raeuscher; Hao-Jie Zhu; John S. Markowitz (Medicinal Chemistry Research, 2025)

Fabrication of nanomagnetite/graphitic carbon nitride composite for adsorption and photo-Fenton decomposition of methylene blue dye - A. M. Awad; G. A. El-Naggar; A. F. Hassan (International Journal of Environmental Science and Technology, 2025)
Pollution caused by synthetic dyes is an urgent issue, necessitating the development of highly effective and environmentally friendly solid adsorbents and catalysts. Herien, nanomagnetite/graphitic carbon nitride composite (NgCN) was developed for the adsorption and photo-Fenton breakdown of methylene blue. The formed NgCN composite has low band gap energy (2.14 eV), high surface area of 94.9 m 2 /g, various chemical surface functional groups, and a TEM average particle size of 10 nm. The adsorption and Fenton approach were studied under several application circumstances. The Langmuir maximum adsorption capacity was verified by NgCN (80.65 mg/g) at pH = 6, and the adsorption was well-applied by Langmuir, Temkin, and Freundlich, as adsorption isotherm models. The kinetic experiments proved the application of nonlinear PSO and Elovich models, and 6 h is the optimum adsorption equilibrium time. The degradation data from Fenton and photo-Fenton show that NgCN is more effective than nanomagnetite (Ng) and graphitic carbon nitride ( g -C 3 N 4 ). Methylene blue breakdown exhibits 100% using NgCN catalyst under UV light at 40 °C, at 40 min of the catalytic activity. Kinetic and thermodynamics of MB decomposition by photo-Fenton verified the PFO, nonspontaneous, and endothermic catalytic procedure. Throughout eight photo-Fenton cycles, the reusability of NgCN declined by only 4.0%. The NgCN demonstrated significant dye adsorption and decomposition efficacy at varying pollutant concentrations. The fabricated material is a promising solid adsorbent as well as a photo-Fenton catalyst for the removal of organic pollutants.

Sustainable bi-layer membrane for efficient interfacial solar steam generation: Silver‑carbon core-shell nanoparticles for enhanced light absorption and stability - Salma M. Abo Kamar; Amr Awad Ibrahim; Soheir A. EL-Hakam; E.A. El-Sharkawy; Awad I. Ahmed; Mina Shawky Adly (Desalination, 2025)

Development of a real-time fDOM-based coagulant dosing system: Beta-testing and model implementation in drinking water treatment plants - Hiua Daraei; Edoardo Bertone; Rodney A. Stewart; Michael Bartkow; John Awad; Josh Soutar; Kathy Cinque; Jonathan Creamer; John Van Leeuwen (Chemical Engineering Journal, 2025)

Pioglitazone mitigates acetic acid-induced colitis in rats via epigenetic-modulation and antioxidant mechanisms - Suzan Awad AbdelGhany Morsy; Lobna M. M. A. Abd El Mottelib; Sara Assem; M. M. Abd El Aziz; Anne H. Elgeziry (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Simvastatin loaded surface-decorated 3D-dendritic mesoporous silica nanoparticles for enhanced antihyperlipidemic activity: in vitro and in vivo appraisal - Abdulsalam M. Kassem; Elsaied H. Barakat; Maged K. Elsayad; Sherif E. Emam; Tarek M. Ibrahim; Ayman Salama; Mohammed Elmowafy; Nabil K. Alruwaili; Omar Awad Alsaidan; Mohamed A. Abdelgawad (Drug Delivery and Translational Research, 2025)

Potential applications of lactic acid bacteria from Egyptian dairy products as novel antioxidant and anticancer agents - Reham A. Madian; Amel A. Ibrahim; Mohamed Yacout; Sameh Awad; Sarah A. Aggag (Biotechnology Letters, 2025)

Multifaceted analysis of cymothoids parasitism, environmental stressors and heavy metal bioaccumulation dynamics in mediterranean farmed fish in Egypt - Mohamed A. Atwah; Mohsen A. Khormi; Awad A. Abdelbaky; Ola Hasan Abd El Megeed; Ali M. Aborasain; Mai A. Salem; Mohamed A. Soliman; Hanan S. Khalefa; Hanan H. Abd-El Hafeez; Mohamed Abdelsalam (Aquaculture International, 2025)
This study investigated the interactions between cymothoids parasitism, environmental stressors, and heavy metal bioaccumulation in commercially farmed fish in the Deeba Triangle area, Egypt. Over 600 fish, comprising gilthead seabream ( Sparus aurata ) and two mullet species ( Mugil cephalus and Liza ramada ), were examined during spring and summer 2023. Seasonal variations in cymothoids parasite infestation showed higher prevalence during spring ( S. aurata : 37%, mullets: 100%) compared to summer ( S. aurata : 20%, mullets: 80%). Morphological and molecular characterization identified the parasite as Livoneca redmanii , with mitochondrial 16S rRNA sequencing revealing 98.73% similarity among isolates (PQ580903-PQ580904). Water quality analysis of aquaculture ponds showed suboptimal conditions compared to the source irrigation canal, including elevated unionized ammonia (0.024–0.042 mg/L vs. 0.012 mg/L) and reduced dissolved oxygen (4.8–5.2 mg/L vs. 6.8 mg/L). Heavy metal accumulation followed consistent tissue-specific patterns (liver > gills > muscle) across five metals (Pb, Fe, Cu, Cd, Mn), with M. cephalus demonstrating the highest bioaccumulation potential. In M. cephalus liver tissue, transfer factors for Cu (175) and Fe (15.45) indicated significant metal retention. Correlation analysis in M. cephalus tissues revealed strong positive relationships between Cu-Fe ( r = 0.88) and Fe–Mn ( r = 0.78). The human health risk assessment indicated that muscle tissue consumption across all species was within safe limits (THQ ≤ 1.0). This integrated analysis provides insights into species-specific management strategies in Mediterranean aquaculture.

Sustainable and eco-friendly packaging films based on poly vinyl alcohol incorporated with Chrysanthemum frutescens extract - Mona M. AbdelMohsen; Hebat-Allah S. Tohamy; Sally A. Abdel-Halim; Hassan M. Awad; Mohamed El-Sakhawy (Natural Product Research, 2025)

Botulinum toxin type A: Efficacy in the management of lower limb spasticity in children with genetic disorders - Mohamed Ashraf; Dina Amin Saleh; Salma M Bakr; Mohamed Ali; George Halim; Marwa A Nassef; Nermine Farouk; Tamer M Sabry; Ahmed Abdellatif Awad; Mostafa G Mahran; Walid Abdel Ghany (Next Research, 2025)

Optical and Photocatalytic Behavior of Sonochemically Synthesized MgFe2O4/BiOBr Nanocomposites for Light-Induced Degradation of Organic Dyes - Rusul A. Ghazi; Mushtaq Ali Hussein; Ali Abbasi; Haneen Majed Saheb; Shaymaa Awad Kadhim; Hossein Khojasteh; Masoomeh Sadat Fini; Kamran Heydaryan (Journal of Fluorescence, 2025)

Assessing the operational features of bus rapid transit at innovative roundabouts: an integrated BWM-MABAC method - Taqwa I. Alhadidi; Farah A. Awad; Roza Hindawi; Asmaa Alazmi (Innovative Infrastructure Solutions, 2025)

Depositional and diagenetic drivers of heterogeneous reservoir quality in the Neogene strata of the Red Sea (Egypt) - Ahmed Ali; Ahmed Awad Abdelhady; Ramadan S. A. Mohamed; Douaa Fathy; Mohamed Hashem; Mohamed S. Ahmed; Sherif M. Aboueldahab; Mahmoud M. Khalil; Mohamed H. Farag (Carbonates and Evaporites, 2025)

Protective role of curcumin and selenium nanoparticles against aluminium chloride-induced hepatorenal toxicity in rats - Safaa M. Awad; Yasser A. Attia; Akaber T. Keshta; Shimaa H. Watad; Eman Rashad; Hassan Elsayed; Shams H. Abdel-Hafez; Aziza T. Fathy (Journal of Molecular Histology, 2025)

Translational potential of GADD45α: biomarker and therapeutic target in age-associated neurodegeneration and longevity - Imran Kazmi; Fahad A. Al-Abbasi; Mustafa Zeyadi; Misbahuddin Rafeeq; Alaa Hamed Habib; Johar Iqbal; Sami I. Alzarea; Omar Awad Alsaidan; Muhammad Shahid Nadeem (Biogerontology, 2025)

The Role of MicroRNAs in Neurodegeneration: Insights from Huntington’s Disease - Reda M. Mansour; Abanoub A. S. Shaker; Ahmed I. Abulsoud; Sherif S. Abdel Mageed; Alaa Ashraf; Elsayed G. E. Elsakka; Mohammed. I. Dahab; Mohamed M. Sadek; Farah A. Awad; Radwa H. Lutfy; Hanan Elimam; Ahmed H. I. Faraag; et al. (Molecular Neurobiology, 2025)

Torsional irregularity of NSC and HSC asymmetric multistory 3-D buildings - Ahmed M. Yousef; Ahmed A. Ghaleb; Doaa M. Awad; Mohamed Ghannam (Innovative Infrastructure Solutions, 2025)
The reliability of the criteria adopted by the seismic codes in the United States (ASCE/SEI-7-16), in Europe (EC-8) and Egypt (ECP201-2012), that are used in distinguish torsionally irregular from torsionally regular Normal-Strength Concrete (NSC) and High-Strength Concrete (HSC) multistory 3-D buildings have been studied. The Static Equivalent Lateral Force (SELF) methods used by these codes for predicting the torsional moments have been examined when applied to NSCand HSCtorsionally asymmetric multistory buildings. Finite element model has been used to solve the nonlinear equations of motions for two multistory buildings examples with different eccentricity (e equal to 0.10L i , 0.15L i and 0.20L i ) and constructed from NSC ( $$f_{c}^{′ }$$ f c ′ = 25 N/mm 2 ), HSC( $$f_{c}^{′ }$$ f c ′ up to 75 N/mm 2 ) and VHSC ( $$f_{c}^{′ }$$ f c ′ up to 100 N/mm 2 ). Many different earthquake records have been used in the seismic analysis. The results showed that the criteria adopted by ASCE/SEI-7-16 so as to distinguish torsionally regular from torsionally irregular NSC, HSC and VHSC multistory buildings are the most reliable and more simple and accurate when compared with the methods adopted by EC-8 and ECP201-2012. The provisions of ECP201-2012 for determination of the torsional irregularity of a building depending on the calculated structural eccentricity (between C. M. and C. R.) may lead to unsafe results. Using the SELF methods of the studied seismic codes in predicting the torsional moments of some torsionally symmetrical and torsionally asymmetrical multistory buildings constructed from NSCand HSCmay lead to unsafe and unconservative predictions. The value of the accidental eccentricity adopted by the studied seismic codes underestimated the torsional moments predicted using SELF methods of the studied codes in some torsionally symmetrical and torsionally asymmetrical multistory buildings.

Evaluation of chalcones as new glycogen phosphorylase inhibitors – an in-vitro and in-silico approach - Talal Ahmed Awad; Fatima Alfatih; Muhammad Shafiq; Mohnad Abdalla; Samia T. Al-Shouli; Amani Bashir; Maaweya E. Awadalla; Hassan A. Alhazmi; Mohammed Albratty; Hafiz A. Makeen; Asaad Khalid; Zaheer Ul-Haq (Natural Product Research, 2025)

Except for Robust Outliers, Rapamycin Increases Lesion Burden in a Murine Model of Cerebral Cavernous Malformations - Roberto J. Alcazar-Felix; Robert Shenkar; Christian R. Benavides; Akash Bindal; Abhinav Srinath; Ying Li; Serena Kinkade; Tatiana Terranova; Evon DeBose-Scarlett; Rhonda Lightle; Dorothy DeBiasse; Hanadi Almazroue; et al. (Translational Stroke Research, 2025)

Lysozyme Peptides as a Novel Nutra-Preservative to Control Some Food Poisoning and Food Spoilage Microorganisms - Adham M. Abdou; Dina A. B. Awad (Probiotics and Antimicrobial Proteins, 2025)
Foodborne illnesses and microbial food contamination are crucial concerns and still issues of great worldwide concern. Additionally, the serious health hazards associated with the use of chemical preservatives in food technology. Lysozyme (Lz) is an active protein against Gram-positive bacterial cell wall through its muramidase lytic activity; however, several authors could identify some antimicrobial peptides derived from Lz that have an exaggerated and broad-spectrum antibacterial activity. Therefore, a lysozyme peptides preparation (LzP) is developed to broaden the Lz spectrum. In this work, we investigated the potential efficacy of LzP as a novel Nutra-preservative (food origin) agent against some pathogenic and spoilage bacteria. Our results showed that LzP demonstrated only 11% of the lysozyme lytic activity. However, LzP exhibited strong antibacterial activity against Escherichia coli , Salmonella enteritidis , and Pseudomonas species, while Salmonella typhi and Aeromonas hydrophila exhibited slight resistance. Despite the lowest LzP concentration (0.1%) employed, it performs stronger antibacterial activity than weak organic acids (0.3%). Interestingly, the synergistic multi-component formulation (LzP, glycine, and citric acid) could inhibit 6 log 10 cfu/ml of E. coli survival growth. The effect of heat treatment on LzP showed a decrease in its antibacterial activity at 5 and 67% by boiling at 100 °C/30 min, and autoclaving at 121 °C/15 min; respectively. On the other hand, LzP acquired stable antibacterial activity at different pH values (4–7). In conclusion, LzP would be an innovative, natural, and food origin preservative to control the growth of food poisoning and spoilage bacteria in food instead chemical one.

Towards sustainability and circular economy: conceptual design model for the water-energy-food nexus in Ferdaws Village, Western Desert, Egypt - Noha M. Mashaal; Mohamed A. Abdelzaher; Mohamed M. Awad; Khalid Z. Elwakeel; Ahmed A. Hassan (Innovative Infrastructure Solutions, 2025)
Sustainable management of natural resources is a pressing global challenge that requires the prevention of loss and waste. Egypt is facing an acute water crisis due to insufficient water supplies throughout the country. To address this issue, it is essential to implement a range of solutions to improve the situation. This study aims to alleviate the stress on multiple resources and environmental impacts in one of Egypt's earliest reclaimed areas (Wadi El-Natrun, Western Desert), by applying systematic modeling to achieve sustainable development objectives and mitigate resource stress. To promote a more sustainable and resilient future, a pilot model ecovillage has been designed for a community of three thousand inhabitants, promoting integrated resource management and considering the Water-Energy-Food (WEF) nexus concept. The ecovillage design incorporates collaborative engagement of groundwater reservoirs for water supply, agricultural production for food demands, power generation, and community sensitivity. Evaluating key aspects related to water supply, power generation, agricultural production, and environmental impact within the proposed pilot design aims to provide insights into the complex interactions among these systems. A four-step methodology for evaluating and implementing the nexus at a local level, which includes identifying linkages, mapping interconnections, focusing on core foundations, and applying the findings to improve project execution was investigated. An understanding of the WEF nexus, demonstrating how such frameworks can enhance the management of scarce resources was provided. The “TORAY DS2” design is employed to analyze model parameters and quantify their values. The study’s findings aim to support decision-makers and stakeholders in developing effective strategies to navigate the complexities of the WEF Nexus, promoting optimal resource management. These findings are promising, indicating a low environmental risk while aligning with both the WEF Nexus and the Sustainable Development Goals.

In Vitro and In Vivo Appraisal of Glycerylmonostearate/chitosan Hybrid Nanocapsules As Peroral Delivery System of Simvastatin - Mohammed Elmowafy; Khaled Shalaby; Nabil K. Alruwaili; Omar Awad Alsaidan; Mohammed H. Elkomy; Mohamed A. Abdelgawad; Ehab M. Mostafa; Ayman Salama; Abdulsalam M. Kassem; Mohamed F. Ibrahim; Mahran Mohamed Abd El-Emam (AAPS PharmSciTech, 2025)

Combustion characteristics of hydrogen, ammonia, and their blends: A review - James K. Moses; Terungwa A. Tivfa; Naef A.A. Qasem; Awad B.S. Alquaity (Fuel, 2025)

Sponge-like fluorapatite/expanded graphite@ agar biohydrogel with self-healing and salt resistance ability for solar steam and electricity cogeneration - Salah Orabi; Amr Awad Ibrahim; Ahmed Gebreil; Doaa A. Kospa (Desalination, 2025)

Improving yield and irrigation water productivity of green beans under water stress with agricultural solid waste-based material of compacted rice straw as a sustainable organic soil mulch - Amal E. Awad; Mohamed E. Abuarab; R. E. Abdelraouf; Gomaa A. Bakeer; Mohamed A. El-Shawadfy; R. Ragab (Irrigation Science, 2025)
This research aimed at water saving in irrigation by applying deficit irrigation using two strategies, standard drip and partial root drying (PRD), while applying organic and plastic mulch over two growing seasons of green beans. A field experiment was conducted in 2022 and 2023, using four irrigation treatments supplying 100% of the irrigation requirement (IRg), 75% IRg, 50% IRg, and 50% IRg—PRD, and four soil mulching treatments: uncovered soil (UC), plastic mulch (PM), rice straw mulch (RSM), and compacted rice straw mulch (CRSM). The combined effect of deficit irrigation strategies and soil mulching showed that the maximum irrigation water productivity (IWP) of 5.56 kg m −3 was achieved under 50% IRg—PRD & CRSM for both growing seasons, followed by 50% IRg—PRD & RSM and 50% IRg—PRD & PM, with 5.19 and 4.96 kg m −3 , respectively. The highest yield of 8936 kg ha −1 was achieved with 50% IRg—PRD & CRSM, followed by 8914 kg ha −1 and 8898 kg ha −1 with 100% IRg & CRSM and 75% IRg & CRSM, respectively. The lowest yield of 6009 kg ha −1 was obtained with 50% IRg & UC. The highest soil moisture content was observed under 100% IRg & CRSM. The application of organic mulches was found to be particularly effective in conserving soil moisture due to enhanced infiltration, improved retention capacity, and suppression of weed growth, ultimately fostering optimal crop development and higher yield. The results of soil temperature variations beneath soil mulches showed that CRSM is effective in alleviating plant water stress, lowering the temperature below the cover and reducing water loss through evaporation from the soil surface. The combination of 50% IRg—PRD & CRSM produced plants with enhanced plant height, fresh and dry weight, leaf area, pod length, and green bean weight, as well as the highest vegetative growth indices. Generally, the organic mulching increased soil temperature, soil moisture, IWP, and green bean production.

Efficacy of curcumin-selenium nanoemulsion in alleviating oxidative damage induced by aluminum chloride in a rat model of Alzheimer’s disease - Safaa M. Awad; Yasser A. Attia; Hassan ElSayed; Shams H. Abdelhafez; Akaber T. Keshta; Eman Rashad; Heba M. A. Khalil; Aziza T. Fathy (Journal of Molecular Histology, 2025)

Phytochemicals in pomegranate peel extract attenuate oxidative damage in rats exposed to fipronil - Awad R. Abd Elfatah; Marwa E. Hassan; Yasmin E. Abdel-Mobdy; Osama M. Abd El fatah; Emam A. Abdelrahim; Mosaad A. Abdel-Wahhab (Pesticide Biochemistry and Physiology, 2025)

The Gastroprotective Effects of Salvia indica L. and Selenium In Vivo Study - Talal Salem Al-Qaisi; Ahmed A. J. Jabbar; Mohammed M. Hussein M. Raouf; Parween Abdul-Samad Ismail; Ramzi A. Mothana; Hanan M. Al-Yousef; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Musher Ismael Saleh; Mohammed Awad; Mohamad Fawzi Mahomoodally (Biological Trace Element Research, 2025)

Curating Benzothiophene Experimental Absorption and Emission Spectra to Design Fluorescent Organic Polymer Chemical Space: A Machine Learning Quest - Shaimaa H. Mallah; Azal S. Waheeb; Abrar U. Hassan; Masar A. Awad; Ayad R. Jalfan; Ashraf Y. Elnaggar; Islam H. El Azab; Mohamed H. H. Mahmoud (Journal of Fluorescence, 2025)

Persimmon (Diospyros kaki L.) leaves accelerates skin tissue regeneration in excisional wound model: possible molecular mechanisms - Talal Salem H. Al-Qaisi; Ahmed A. j. Jabbar; Mohammed M. Hussein M. Raouf; Parween AbdulSamad Ismail; Ramzi A. Mothana; Mohammed F. Hawwal; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Musher Ismael Saleh; Mohammed Awad (Journal of Molecular Histology, 2025)

Performance of a recirculating aquaponic system in vegetable production using river fish (Nile tilapia) - Mohamed I. Saber; Noha A. Mahgoub; Yasser M. Awad; Samira R. Mansour (Euro-Mediterranean Journal for Environmental Integration, 2025)

Degradation of ciprofloxacin using CoFe2O4@three-dimensional TiO2@graphene aerogels composite: kinetic, reusability, mineralization, degradation pathway, and toxicity assessment - Fatemeh Zisti; Irwanjot Kaur; Sameer A. Awad; Nizomiddin Juraev; Dmitry Olegovich Bokov; Hamad AlMohamadi; Carlos Rodriguez-Benites; Merwa Alhadrawi; Salah Hassan Zain Al-Abdeen; Davoud Balarak (Environmental Science and Pollution Research, 2025)

In vitro and Silico Exploration of the Insecticidal Properties of Lavandula multifida L. Essential Oil and its Binary Combinations with Cyantraniliprole and Emamectin benzoate on Spodoptera frugiperda (Lepidoptera: Noctuidae) - Moataz A.M. Moustafa; Nourhan A. El-Said; Fatma S. Ahmed; Alia Amer; Mona Awad; Nawal Abdulaziz Alfuhaid (Crop Protection, 2025)

Highly active nickel-based fibrous silica ZnO (NSZF) catalyst for efficient syngas production through dry reforming of methane - Mohammed Mosaad Awad; Ijaz Hussain; Saheed A. Ganiyu; Khalid Alhooshani (Fuel, 2025)

Enhanced solar-to-steam conversion efficiency using CuO-polyaniline yolk-shell structures - Mennatallah H. Farag; S.A. El-Hakam; Awad I. Ahmed; Amr Awad Ibrahim; Doaa A. Kospa (Desalination, 2025)

Detection and molecular insights into the azurin gene expression post– gamma irradiation in P. aeruginosa - Ebthag M. Awad; Nagwa A. Abdallah; Mona M. K. Shehata; Hala A. Farrag (Archives of Microbiology, 2025)

Correction to: The effects of nano‑selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El‑Aziz; Yasmin A. Reyad; El‑Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

The effects of nano-selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El-Aziz; Yasmin A. Reyad; El-Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

First Record of Five Species of Sea Urchins (Class Echinoidea, Five Orders) From the Gulf of Aden - Mohammed A. Algurabi; Alawi H. MсNoon; Rashidi M. R. Awad; Shima Bakhshalizadeh; Botagoz M. Nasibulina; Tatyana F. Kurochkina; Attaala M. Ali; Syed Sikandar Habib; Francesco Fazio (Marine Ecology, 2025)
The Gulf of Aden (GA) experiences seasonal upwelling phenomena, fostering favorable conditions for diverse marine life. Despite this richness, the known sea urchin species in the Gulf of Aden has been limited to the common long‐spined ( Diadema paucispinum ). Our study aimed to explore and document sea urchin diversity in this region. Through scuba diving and low tide collections from coral reefs and sandbanks, we obtained samples along the Hadhramout coast, spanning from the Qusayr area to the Aden Province coast, including Azizi Island opposite Ras Imran and the sub‐district of the city of Aden. This survey revealed five sea urchin species, expanding the known taxa. For the first time in the Gulf of Aden, we qualitatively registered two regular and three irregular sea urchin species: Heterocentrotus mammillatus (Linnaeus, 1758), Stomopneustes variolaris (Lamarck, 1816), Echinodiscus bisperforatus (Leske, 1778), Clypeaster humilis (Leask, 1778), and Lovenia elongata (Gray, 1845). These findings contribute to our understanding of the Gulf biodiversity and emphasize the need for continued exploration in this region.

Quality maintenance of Washington navel oranges and control of fungal decay using CaCl₂, chitosan, and Rhodotorula mucilaginosa treatments - Mohamed I. Elsayed; Najeeb M. Almasoudi; Mohamed A. Awad; Adel D. Al-Qurashi; Kamal A. M. Abo-Elyousr (Journal of Plant Pathology, 2024)

The Preventive Effect of Zinc Sulfate against Olanzapine-Induced Testicular Toxicity in Male Rats - Hossam Ebaid; Samir A. E. Bashandy; Iftekhar Hassan; Jameel Al-Tamimi; Shimaa Abdallah Haredy; Tharwat Imbabi; Enayat A. Omara; Yousef S. Bashandy; Ezzat M. Awad (Biological Trace Element Research, 2024)
Male infertility is a complex and multifactorial clinical condition affecting a large population attributed to several factors, including perturbation in oxidative stress and the level of essential trace elements. Oxidative stress exerts multiple issues related to reproductive health, including male infertility, decreased sperm motility, sperm DNA damage, and an increased susceptibility to genetic disorders. Besides chemical toxins and food allergens in junk food items, many drugs can also lead to male infertility. Olanzapine (OLZ), a general antipsychotic drug, has also been reported to induce male fertility. A great deal of literature entails that supplementation of zinc can alleviate oxidative stress–related clinical complications, including male infertility. This study investigates the potential protective effects of zinc sulfate (ZnSO4) on OLZ-induced male infertility. In the present study, there were four treatment groups ( n = 6): group 1 as control (without any treatment); group 2 treated with OLZ (10 mg/kg) orally daily for 6 weeks; groups 3 and 4 treated with 50 mg/kg and 100 mg/kg of ZnSO4 respectively in pre-exposed OLZ (10 mg/kg) orally daily for 6 weeks. After completion of the treatment, the biochemical analysis of serum and tissue samples demonstrated that group 2 had compromised levels of antioxidant parameters (superoxide dismutase (SOD), catalase (CAT), and reduced glutathione (GSH)) as well as elevated levels of stress parameters (oxidized glutathione (GSSG), malondialdehyde (MDA), and nitric oxide (NO)) as compared to the control by a significant extent ( p ≤ 0.05). However, supplementation of ZnSO4 significantly corrected all these parameters in a dose-dependent way in groups 3 and 4 ( p ≤ 0.05). Other health indicators, like taurine, enzyme Q10, phosphatidylcholine, ascorbic acid, and vitamin E, were also observed to improve prominently with the supplementation of ZnSO4. Intriguingly, all the fertility parameters (sperm motility, count and level of testosterone) were also found to be significantly enhanced with decreased sperm abnormalities in both the combination groups. The histological evaluation of the testis section also agreed with the biochemical analysis in this investigation. Therefore, the study strongly advocates that supplementation of Zn can ameliorate OLZ-induced male infertility to a significant extent. Graphical Abstract Putative mechanism was involved in a preventive effect of ZnSO4 against OLZ-induced biochemical and histological perturbation in vivo. OLZ generates free radicals to induce oxidative stress-mediated toxicity in all target organs including testes evidenced by alteration in biochemical markers and histology. Zn ions from ZnSO4 act as an antioxidant agent blunting most of the OLZ-perturbed redox markers and histology consequently improving fertility parameters.

Recent advances and future prospects of MXene-based photocatalysts in environmental remediations - Basiru O. Yusuf; Mustapha Umar; Mansur Aliyu; Aliyu M. Alhassan; Mohammed Mosaad Awad; Omer A. Taialla; AbdulHakam Shafiu Abdullahi; Jamilu Nura Musa; Khalid R. Alhooshani; Saheed A. Ganiyu (Journal of Environmental Chemical Engineering, 2024)

A novel mathematical template for developing fDOM probe fluorescence signal correction models for freshwaters - Hiua Daraei; Edoardo Bertone; John Awad; Rodney A. Stewart; Christopher W.K. Chow; Jinming Duan; Amanda Mussared; John Van Leeuwen (Journal of Environmental Sciences, 2024)

Foliar Nourishment with Different Potassium Sources to Maximize Yield Through Improving Nutrient Uptake in Citrus Aurantifolia Trees Grown in Potassium-Deficient Soil - Ahmed A. M. Awad; Hamdy A. Z. Hussein; Asmaa G. A. Abd El Samad; Hussein E. E. Belal; Hamada R. Beheiry (Journal of Soil Science and Plant Nutrition, 2024)
Purpose: Based on its crucial regulatory role in several biochemical processes, potassium (K) is considered to greatly influence fruit yield and quality. Methods: Two field experiments were carried out in two seasons (2021 and 2022) to explore the response of lemon (Baladi cv.) trees grown in K-deficient soil to four different K fertilizer sources applied individually as a foliar spray. K citrate (KC 1 = 1.3 vs. KC 2 = 2.6 g L − 1 ), K nitrate (KN 1 = 1.5 vs. KN 2 = 3.0 g L − 1 ), K tartrate (KT 1 = 1.5 vs. KT 2 = 3.0 g L − 1 ), and K thiosulfate (KS 1 = 1.25 vs. KS 2 = 2.5 g L − 1 ) were applied three times, and the treated trees were compared with untreated trees. This study was established with a randomized complete block design (RCBD) using four replicates. Results: The findings revealed that the KC treatment, regardless of dosage, showed clear superiority in terms of the values for the leaf phosphorus (%), manganese, and zinc contents (mg kg − 1 ), as well as fruit firmness, fruit dry matter, and total soluble solids in both seasons. In second place was the KT treatment, which yielded the best values for fruit length and width in 2021, the best values for leaf nitrogen and iron contents and fruit weight and volume in 2022, and the best values regarding variable fluorescence by maximum fluorescence, relative chlorophyll content (SPAD readings), the photosynthetic performance index, total acidity, and vitamin C in both seasons. Furthermore, the highest total lemon yield and leaf potassium contents were achieved with the KN treatment in both seasons. The heat map illustrating that most of the studied characteristics were positively and significantly correlated with total lemon yield (TLY). Conclusions: The KN treatment, closely followed by the KC treatment, is regarded to be the best treatment for most of the studied trails.

Prevalence of Non-typhoidal Salmonellae in the Retail Chicken Meat in Alexandria, Egypt - Deng Barac; Hussein Mansour; Sameh Awad; Mohamed A Ghazy; Ahmed Abdel-Mawgood (Indian Journal of Microbiology, 2024)

Fog collection rate investigation for a hydrophobic surface and different inclinations of rectangular meshes - Abdullah A. Elshennawy; Magdy Y. Abdelaal; Ahmed M. Hamed; Mohamed M. Awad (Euro-Mediterranean Journal for Environmental Integration, 2024)

Neurotoxicity, Cytotoxicity, and Genotoxicity of Phyto-radio Synthesized Selenium Nanoparticles in Culex pipiens Complex - H. H. Awad; I. Abulyazid; E. M. S. El-Kholy; H. S. Mohammed; H. K. Abdelhakim; A. M. Fadl (Biological Trace Element Research, 2024)
Effective mosquito management strategies are crucial to minimize the number of mosquito-borne diseases. Selenium nanoparticles (SeNPs) are promising in mosquito control because they are effective and eco-friendly rather than synthetic insecticides. The current study was conducted to evaluate the impact of SeNPs on the detoxification enzymes, acetylcholine esterase (AChE), glutathione S-transferase (GST), and α-carboxyl esterase (α-CarE), in larval instars of Culex pipiens complex at the LC 50 concentration. In 3rd instar larvae treated with microwave-assisted selenium nanoparticles (SeNPs-MW) and gamma-assisted selenium nanoparticles (SeNPs-G), it was found that AChE activity was significantly inhibited. On the other hand, significant increases in GST and α-CarE activities were observed. Additionally, genotoxic and ultrastructure studies of midgut epithelial cells in 3rd instar larvae revealed DNA damage and cell lysis, including destruction of the cell membrane, microvilli, and nuclei. These findings suggest that SeNPs have an adverse effect on AChE gene expression, resulting in its downregulation. This downregulation can be attributed to the formation of reactive oxygen species induced by SeNPs that can modulate the host defense mechanism leading to apoptosis and subsequent larval mortality. The present study was the first to use phyto-microwave-assisted and gamma-assisted synthesis of SeNPs which provides an eco-friendly and cost-effective solution to reduce the risk of chemical insecticides. Furthermore, an integrated pest management program (IPM) using nanocides can be successfully developed for mosquito control.

Correction: Comprehensive approach integrating water quality index and toxic element analysis for environmental and health risk assessment enhanced by simulation techniques - Mohamed Hamdy Eid; Mahmoud Awad; Essam A. Mohamed; Tamer Nassar; Mostafa R. Abukhadra; Ahmed M. El-Sherbeeny; Attila Kovács; Péter Szűcs (Environmental Geochemistry and Health, 2024)

Comprehensive approach integrating water quality index and toxic element analysis for environmental and health risk assessment enhanced by simulation techniques - Mohamed Hamdy Eid; Mahmoud Awad; Essam A. Mohamed; Tamer Nassar; Mostafa R. Abukhadra; Ahmed M. El-Sherbeeny; Attila Kovács; Péter Szűcs (Environmental Geochemistry and Health, 2024)
Due to water shortages and the potential impact of Ethiopia’s new dam on the Nile River, Egypt is seeking new water resources. This study assesses the drinking water quality and associated risks from potentially toxic elements (PTEs) in the Quaternary aquifer (QA) in Beni-Suef, Egypt. Using a comprehensive approach, including PHREEQC geochemical modeling, ionic ratios, multivariate statistical analyses, and the integrated weight water quality index (WQI), the study evaluated the sources of ion contamination and the mixing of Nile water with QA. Various indices, such as the Heavy Metal Pollution Index (HPI), ecological Risk Index (RI), Hazard Quotient (HQ), and Hazard Index (HI), were used to assess ecological and health risks. Monte Carlo simulations provided probabilistic assessments of non-carcinogenic risks for adults and children. GIS tools were used to map risk indices, identifying the most deteriorated locations for sustainable management. The hydrochemical analysis revealed water facies including Na–Cl, Ca–Mg–HCO 3 , and mixed types, influenced by carbonate dissolution, ion exchange, and silicate weathering. Contamination sources, particularly in the north and south, were linked to agricultural activities, irrigation return flow, municipal waste, and evaporation. The WQI indicated that 10.14% of samples were extremely poor, 21.7% were poor, 26% were medium, and 42% were good to excellent. PTE contamination varied, with HPI values indicating good water quality in the central area in 53.6% of the collected samples (HPI < 30), but contamination in the north and south is high (HPI > 51). Ecological Risk Index values were below the threshold in 100% of samples (RI < 30), confirming water safety regarding PTEs. In comparison, for hazard index (HI) through oral/ingestion, adults exhibited HI values ranging from 0.012 to 2.16, while children showed higher values, ranging from 0.045 to 8.25. However, the hazard index for oral/ingestion exceeded safe limits in the north and south (HI oral > 1), posing non-carcinogenic risks. Monte Carlo simulations revealed significant risks from oral exposure to manganese (HQ oral > 1), particularly in El-Wasta and El-Fashn, necessitating further treatment and management.

Efficacy and Safety of Ontamalimab in Treating Inflammatory Bowel Disease: a Systematic Review and Meta-Analysis of Randomized Controlled Trials - Abdelaziz A. Awad; Menna M. Aboelkhier; Rashad G. Mohamed; Ahmed W. Abbas; Ahmed W. Hageen; Yousef R. Alnomani; Mohamed Abouzid (Current Pharmacology Reports, 2024)
Purpose of Review Ontamalimab is an anti-MAdCAM-1 monoclonal antibody. It directly restricts the binding of α4β7 + lymphocytes and does not affect the homing of lymphocytes in the central nervous system. Thus, it diminishes adverse effects while blocking their migration into the gut. Several clinical trials have validated the efficacy and safety of ontamalimab for Crohn's disease and ulcerative colitis. However, to date, there is no meta-analysis on the topic. Hence, we are conducting this meta-analysis. Using R version R.3.3, we reported outcomes as risk ratios (RRs) or mean difference (MD) and confidence intervals (CIs). A P -value ≤ 0.05 is considered as statistically significant. Recent Findings The meta-analysis included a total of three studies with 1384 patients. In patients with ulcerative colitis, compared to placebo, ontamalimab had significantly improved clinical remission (RR = 2.17, 95% CI [1.42 to 3.32], P < 0.01), clinical response (RR = 1.79, 95% CI [1.35 to 2.38], P < 0.01), endoscopic response (RR = 2.27, 95% CI [1.55 to 3.31], P < 0.01) and mucosal healing (RR = 2.39, 95% CI [1.63 to 3.50], P < 0.01). No significant differences favoring ontamalimab or the placebo were found regarding safety outcomes. In patients with Crohn's disease, ontamalimab showed superiority over placebo in endoscopic response (RR = 2.00, 95% CI [1.08 to 3.70], P = 0.03). However, ontamalimab was associated with a higher incidence of serious adverse events, and study discontinuations were due to adverse events. Summary Ontamalimab has shown promising results, particularly in patients with moderate to severe ulcerative colitis, as evidenced by better clinical response and remission. However, questions remain about its long-term effectiveness and safety; hence, extended follow-up and more extensive studies are necessary.

Molecular characterization of elite olive cultivars grown in the North region of Saudi Arabia using SCoT, ISSR, and SRAP techniques - Reem M. Alharbi; Nanis H. Gomah; Wafik S.M. Ragab; Nabil S. Awad; Mohamed A. Abdein (Biocatalysis and Agricultural Biotechnology, 2024)

Potentiality of Melatonin for Reinforcing Salinity Tolerance in Sorghum Seedlings via Boosting Photosynthetic Pigments, Ionic and Osmotic Homeostasis and Reducing the Carbonyl/Oxidative Stress Markers - Nesma M. Helal; Hani S. Saudy; Maha M. A. Hamada; Ahmed Abou El-Yazied; Hany G. Abd El-Gawad; Soumya Mukherjee; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Salwa M. El-Sayed; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2024)
Salinity stress has become a major threat to worldwide crop production. Exogenous melatonin (MT) has appeared as a promising treatment against salt stress in several plant species. However, MT effect on the tolerance of sorghum plants under different saline conditions (moderate and severe) remains ambiguous. This study was carried out to explore the impact of MT (0, 50, 100 and 200 µM) as a foliar application on sorghum seedlings grown under moderate and severe saline conditions using sodium chloride, NaCl (75 and 150 µM NaCl). Salinity treatments were applied as solution in sand medium in pots. The results demonstrated that rising salinity level negatively affected plant growth, photosynthetic pigments (chlorophylls and carotenoids), leaf water status and ionic homeostasis (sodium, potassium, and calcium ions). Applied-MT specifically at 100 or 200 µM enhanced the osmotic balance, cell membrane stabilizing and leaf relative water content. These effects were associated with an obvious restriction to the level of hydrogen peroxide, lipid peroxidation (malondialdehyde content) and methylglyoxal. Moreover, antioxidant activities of peroxidase, catalase, superoxide dismutase, and ascorbate peroxidase enzymes were modulated by MT treatments. Molecular docking modeling assessment illustrated top-ranked confirmations between MT and the target antioxidant enzymes. MT forms multiple hydrogen bonds with key amino acid residues for glycine (A: 162), tryptophan (A: 41), leucine (A: 165), tyrosine (A: 235) in the active site of ascorbate peroxidase. The alkyl interactions with leucine (A: 37), arginine (A: 38) and cysteine (A: 168) also contribute to its high affinity. Despite sorghum plant is commonly moderately tolerant to salinity stress, the results of this study confirmed its high sensitivity to a wide range of saline conditions at early growth stages. Melatonin spraying led to improvements in various morphological, physiological and biochemical mechanisms that harmonized together to confer stress resistance to salt-stressed sorghum seedlings.

Postoperative elevated bed header position versus supine in the management of chronic subdural hematoma: a systematic review and meta-analysis - Ibrahim Serag; Mariam Abdelhady; Abdelaziz A. Awad; Ahmed Wageeh; Ahmed Shaboub; Rowan H. Elhalag; Ahmed Aljabali; Mohamed Abouzid (Acta Neurologica Belgica, 2024)
Background Chronic subdural hematoma (CSDH) is a prevalent type of intracranial hemorrhage. Surgical interventions, such as Twist Drill Craniostomy and Burr Hole Craniostomy, are employed for its treatment. However, limited information exists regarding the impact of postoperative head position (supine vs. elevated) on clinical outcomes. We aim to assess whether patients’ head position after surgery influences their prognosis. Method We conducted a PRISMA-compliant systematic review and meta-analysis. Our search encompassed PubMed, Cochrane CENTRAL, Scopus, Web of Science, and Embase databases to identify relevant published studies. Data were meticulously extracted, pooled using a fixed model, and reported as risk ratios (RR) with 95% confidence intervals (CI). Statistical analysis was performed using R and Stata MP v.17. Results Five studies involving 284 patients were included in our meta-analysis. We focused on three primary clinical outcomes, comparing the supine and elevated header positions. Notably, there was no statistically significant difference between the supine and elevated positions in terms of recurrence rate (RR 0.77, 95% CI [0.44, 1.37]), second intervention for recurrence (RR 1.07, 95% CI [0.42, 2.78]) and postoperative complications (RR 1.16, 95% CI [0.70, 1.92]). Conclusion Current studies have proved no difference between supine and elevated bed header positions regarding recurrence rate, second intervention for recurrence, and postoperative complications. Future RCTs with long-term follow-ups are recommended.

A carboethoxy quinoline-Derived Schiff base chemosensor: Crystal structure, selective Hg2+ ion detection and its computational study - Franklin Ebenazer Ambaison; Selva Kumar Ramasamy; Sampathkumar Natarajan; Geetha Venkatesan; Tahani Awad Alahmadi; Ponnusamy Rohini; Anderson A (Environmental Research, 2024)

Atorvastatin loaded lecithin-coated zein nanoparticles based thermogel for the intra-articular management of osteoarthritis: in-silico, in-vitro, and in-vivo studies - Heba Amin Elgendy; Amna M. A. Makky; Yara E. Elakkad; Heba H. Awad; Mahmoud A. El Hassab; Nihal Farid Younes (Journal of Pharmaceutical Investigation, 2024)
Purpose Up-to-date literature offers limited data about utilizing atorvastatin calcium (ATV) as a promising chondroprotective agent in osteoarthritis (OA). So, this study aims to develop a depot intra-articular (IA) delivery system for ATV to enhance its deposition in the articular joint. Methods A 3 3 D-optimal design was implemented to prepare ATV-loaded lecithin-coated zein nanoparticles. The optimized formulation (Opt-LCZN) was selected and imaged using a transmission electron microscope according to the desirability value. Various in-vitro and in-silico studies were conducted to evaluate the features of Opt-LCZN. Additionally, it was loaded into an injectable thermogel (Opt-LCZN-thermogel) and evaluated in-vivo in OA-induced Sprague Dawley rats. Results The Opt-LCZN showed entrapment efficiency of 70.00 ± 2.96%, particle size of 191.95 ± 17.42 nm, zeta potential of − 20.12 ± 0.79 mV, and polydispersity index of 0.25 ± 0.01. The docking studies revealed favorable binding of zein and ATV, confirmed by molecular dynamics simulation. The morphological examination displayed a bilayer spherical structure formed of a zein core enclosed by a lecithin coat. Furthermore, the formulated Opt-LCZN-thermogel achieved a remarkable sustained release profile, with nearly 50% of the drug being released over 144 h. Opt-LCZN-thermogel showed a significant reduction in inflammation in OA-induced rats, confirmed by knee joint swelling and knee bend test results, in addition to the pro-inflammatory and anti-inflammatory mediators’ levels. The protective effect of ATV can be markedly observed through histopathological examination. Conclusion Based on these outcomes, the formulated IA delivery system of ATV can be presented as an excellent candidate for ameliorating OA. Graphical abstract

Land surface temperature and NDVI patterns in the petroleum and non-petroleum regions in Southern Iraq (Al-Basra) - Safaa A. Kadhum; Ahmed Awad; Salwan Ali Abed; Mohammed Janaydeh; Ahmad Al-Khayat; Ali Al-Hemoud (Environment, Development and Sustainability, 2024)

New uricase producing Stenotrophomonas isolate recovered from a hot well in western south Egypt: Strain identification, Statistical optimization of enzyme production and In vitro application in gout treatment - Asmaa I. El-Shazly; Hassan M. Awad; Amira A. Gamal; Douaa H. Abdel-Aziz; Azza M. Noor El-Deen (Biocatalysis and Agricultural Biotechnology, 2024)

The vegetation around the foothills of the Hijaz Mountains, Saudi Arabia - Nick Hofland; Mohamed Z. Hatim; Jacob Thomas; John A. M. Janssen; Awad S. Alharti; Ahmed H. Alfarhan; Abdulrahman A. Alatar; Joop H. J. Schaminée; Mohamed A. El-Sheikh (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)
Despite Saudi Arabia being an interesting area from a floristic perspective, its vegetation is still relatively poorly studied. This certainly applies to the Hijaz Mountains and adjacent coastal zones. We aim to describe the flora and vegetation of the foothills of the Hijaz Mountains regarding the environmental conditions. Hijaz Mountains and adjacent coastal zones, Saudi Arabia. We studied the vegetation at the Hijaz Mountains’ foothills along two transects of vegetation surveys, one along the coast and one more inland. In addition, soil samples were taken and analyzed for soil texture, pH, electrical conductivity, organic matter, calcium carbonate and the concentration of the elements N, Na, K, Ca, Mg, Fe and Mn were determined. We calculated the data clustering tendency (Hopkins’ test analysis) and its optimal number of clusters (Elbow method). We used modified TWINSPAN to cluster the data and validated the resulting communities using the Silhouette algorithm. Seven plant communities resulted, each one dominated by a different plant species, namely: Haloxylon salicornicum , Lycium shawii , Senegalia hamulosa , Vachellia tortilis , Zygophyllum coccineum , Vachellia flava and Stipagrostis plumosa , and were described based on their floristic composition and could be further grouped into three vegetation clusters. The communities had varying ranges of occurrence in the study area, some dominating certain sections, with latitude and altitude being the biggest distinguishing environmental variables between the communities. We present a description of the vegetation of the Hijaz Mountains foothills. Our study is considered an important basis for decision-making of nature conservation and in-depth surveys of the area. Graphic abstract

Comparison of various hormone combinations and the potential of chitosan nanoparticles for growth stimulation in Astragalus spp. - Haifa A. S. Alhaithloul; Nabil S. Awad; Tahsin Shoala; Mesfer M. Alqahtani; Fahad Mohammed Alzuaibr; Abdulrahman Alasmari; Mohamed A. Abdein (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Integrating facies, mineralogy, and paleomagnetism to constrain the age and provenance of Paleozoic siliciclastic sedimentary rocks along the northern Gondwana margin: insights from the Araba and Naqus formations in western Gulf of Suez, Egypt - Ashraf M. Al-Nashar; Nabil A. Abdel Hafez; Mohamed W. Abd El-Moghny; Ahmed Awad; Sherif Farouk; Haitham M. Ayyad (International Journal of Earth Sciences, 2024)
The depositional ages and provenance of the Paleozoic Araba and Naqus Formations along the northern Gondwanan margin in Egypt have remained uncertain due to a lack of index fossils. Resolving this issue is crucial for understanding regional geology during deposition and subsequent tectonic development. We integrate detailed facies analysis, anisotropy of magnetic susceptibility (AMS), paleomagnetism, and mineralogical data to elucidate the genesis and depositional ages of the Araba and Naqus Formations. Petrographic analyses identified seven distinct facies types, providing insights into sedimentary textures, maturity, and sources, with contributions from igneous and metamorphic sources indicated by heavy minerals. X-ray diffraction (XRD) analysis identified accessory minerals such as quartz, goethite, kaolinite, hematite, and anatase. Paleomagnetism isolated two magnetic components ( C A and C N ) providing the first robust paleo pole positions at Lat. = 70.8° N, Long. = 308.2° E and Lat. = 37.8° N, Long. = 233.1° E, indicating Cambrian and Carboniferous ages for the Araba and Naqus formations, respectively. Thermal demagnetization constrained these dates using established polarity timescales. Mineralogical data indicated that the Araba Formation originated from an igneous source, while the Naqus Formation had a mixed metamorphic-igneous provenance. The integrated AMS and paleomagnetic data reveal evidence of post-depositional deformation. Specifically, the clustering of maximum AMS axes in the NW–SE direction for both formations, suggests the initial presence of a primary depositional fabric. However, prevalent tectonic activity during the Cenozoic appears to have overprinted and modified this fabric through deformation related to rifting of the Gulf of Suez region. Through this novel multi-proxy approach, we have resolved long-standing uncertainties regarding the formations' depositional ages. Our study thereby provides the first chronostratigraphic framework for these strategically important sedimentary units, significantly advancing understanding of regional Paleozoic geology. Graphical abstract

Climate changes and food-borne pathogens: the impact on human health and mitigation strategy - Dina A. Awad; Hazem A. Masoud; Ahmed Hamad (Climatic Change, 2024)
Climate change has emerged as a major pressing global issue with far-reaching implications for human health, such as the emerging and spread of food-borne pathogens. Food-borne pathogens are microorganisms that can cause illness in humans, from mild discomfort to life-threatening diseases, through the consumption of contaminated food or water. The impact of climate change on food-borne pathogens is multifaceted and includes changes in the environment, agriculture, and human behavior. This review article examines the effect of climate change on food-borne pathogens, explores the connection between climate change and food-borne illness, records the current evidence on the effects of climate change on food-borne pathogens and potential consequences for human health, highlights knowledge gaps and areas for further research, and summarizes the strategies for mitigation and adaptation. Understanding the delicate relationship between climate change and food-borne infections makes it possible to maintain food systems and defend the health and well-being of populations worldwide.

Green Synthesized Zinc Oxide Nanoparticles Attenuate Acrylamide-Induced Cardiac Injury via Controlling Endoplasmic Reticulum Stress–Associated Apoptosis Through ATF3/CHOP/BCL2 Signaling in Rats - Manal Alosaimi; Yasmina M. Abd-Elhakim; Amany Abdel-Rahman Mohamed; Mohamed M. M. Metwally; Tarek Khamis; Wafa S. Alansari; Areej A. Eskandrani; Walaa M. Essawi; Marwa M. Awad; Rehab A. A. El-Shaer; Sarah Ibrahim; Mohamed A. Nassan; et al. (Biological Trace Element Research, 2024)

Sex comparison of oxidative stress, mitochondrial dysfunction, and apoptosis triggers induced by single-dose Abamectin in albino rats - Hossam El Din H. Abdelhafez; Amr A. Abdallah; Reda K. Abdel-Razik; Nadia A. Hamed; Ahmed Elshatory; Walaa Awad; Abdel Azeim A. Khalaf; Aya M. Mekkawy (Pesticide Biochemistry and Physiology, 2024)

CoFe2O4/PANI/MWCNTs ternary hybrid composites. Synthesis, characterization, the effect of MWCNTs ratio and dye removal capability - Mohamed A. Gabal; Ebtesam Al-Mutairi; Yaser M. Al Angari; Mohamed Abdel Salam; Ayman Awad; Amani A. Al-Juaid; Abdu Saeed (Environmental Science and Pollution Research, 2024)

Towards Sustainable Pest Management: Toxicity, Biochemical Effects, and Molecular Docking Analysis of Ocimum basilicum (Lamiaceae) Essential Oil on Agrotis ipsilon and Spodoptera littoralis (Lepidoptera: Noctuidae) - Mona Awad; Nawal Abdulaziz Alfuhaid; Alia Amer; Nancy N. Hassan; Moataz A. M. Moustafa (Neotropical Entomology, 2024)
Over the last decade, essential oils (EOs) have become potential ingredients for insecticide formulations due to their widespread availability and perceived safety. Therefore, this study aimed to evaluate the toxicity and biochemical efficacy of basil ( Ocimum basilicum ) (Lamiaceae) against two destructive pests Noctuidae, Agrotis ipsilon (Hufnagel) and Spodoptera littoralis (Boisduval) (Lepidoptera: Noctuidae). In addition, a molecular docking study was performed to gain insight into the binding pattern between glutathione S-transferase (GST) and linalool, the main component of EO. GC–MS analysis of O. basilicum EO revealed that linalool is the most abundant compound (29.34%). However, the toxicity tests showed no significant difference between the values of LC 50 of O. basilicum EO to A. ipsilon and S. littoralis . On the other hand, the sublethal experiments indicated that treating the second instar larvae with LC 15 or LC 50 values of O. basilicum EO significantly prolonged the larval duration in both insects, compared to the control. Regarding the biochemical effect of O. basilicum EO, the treatments significantly impacted the activity of detoxification enzymes. A notable elevation in glutathione S-transferase (GST) activity was recorded in A. ipsilon larvae compared with a reduction in S. littoralis larvae. The molecular docking analysis revealed that linalool bonded with the amino acid serine (SER 9) of GST, indicating its binding affinity with the enzyme. The obtained results could offer valuable insights into the mode of action of O. basilicum and can encourage the adoption of sustainable pest control practices that incorporate essential oils.

Nanoparticles synergy: Enhancing wheat (Triticum aestivum L.) cadmium tolerance with iron oxide and selenium - Fu Chen; Feifei Jiang; Mohammad K. Okla; Zahid Khorshid Abbas; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Mostafa A. Abdel-Maksoud; Leobardo Manuel Gómez-Oliván (Science of The Total Environment, 2024)

The Middle-Upper Eocene in the Northern Plateau of the Bahariya Depression, Western Desert (Egypt) and correlation with other Tethyan sectors - Ehab M. Assal; Hamdalla A. Wanas; Heba A. Abou Awad (Marine and Petroleum Geology, 2024)

Impact of Calcination Temperature on Structural and Optical Properties and Photocatalytic Efficiency of Ni0.33Cu0.33Zn0.33Fe2O4 Nanoparticles in Aniline Degradation - Mostafa A. Farhat; Amani Aridi; Roaa Yassine; Zouheir Bitar; Ramadan Awad (Water, Air, & Soil Pollution, 2024)

Evaluation of the subsurface structural features of the Farafra Oasis, western desert, Egypt using aeromagnetic data - Mohamed M. Khalifa; Waheed H. Mohamed; Mahmoud A. El Ammawy; Ayman I. Taha; Ahmed Awad; Ahmed Awad Orchid (Modeling Earth Systems and Environment, 2024)

Silica-embedded nutrient-doped biochar improves nutrient availability and safflower (Carthamus tinctorius L.) growth in cadmium- and lead-contaminated soil - Munir Ahmad; Hamed Ahmed Al-Swadi; Jahangir Ahmad; Muhammad Usama; Mohammed Awad Mousa; Nahrir M. A. Lubis; Muhammad Imran Rafique; Mohammad I. Al-Wabel; Abdullah S. Al-Farraj (Journal of Soils and Sediments, 2024)

THMs removal from aqueous solution using hydrochar enhanced by chitosan nanoparticles: preparation, characterization, kinetics, equilibrium studies - H. S. Jahin; A. Hesham; Y. M. Awad; S. El-Korashy; G. Khairy (International Journal of Environmental Science and Technology, 2024)
In this study, novel green and economical techniques were established to synthesize modified banana peel hydrochar (HBP) through hydrothermal carbonization. Chitosan nanoparticles, a green adsorbent with multiple features, were prepared, characterized, and used to enhance the performance of the hydrochar in THMs removals. The optimal method for hydrothermal carbonization was determined based on previously cited methods. The dried banana peels and HBP were characterized using Fourier transform infrared spectrometer (FTIR), pH, zero point of charge, and bulk density. The prepared chitosan nanoparticles were characterized using scanning electron microscope (SEM), transmission electron microscope (TEM), and zeta potential techniques. The average size of chitosan nanoparticles was 12.1 nm, and a 1:1 mixture of HBP and chitosan nanoparticles was used for the removal of THMs from an aqueous solution. The concentrations of THMs were measured using gas chromatography, and the effect of THMs’ initial concentrations, adsorbent doses, temperature, and pH value on the adsorption capacity was studied. The results showed that the 1:1 mixture of HBP and chitosan nanoparticles was an efficient adsorbent for removing THMs from aqueous solutions. This adsorbent was found to be effective in removing THMs from the aqueous solution, even at low temperature and pH values, with an estimated maximum sorption capacity ( q m ) of 588.23 g g −1 , exceeding numerous other adsorbents previously studied, and the regression coefficient ( R 2 = 0.9959) for data fitting with the Freundlich isotherm. This research has the potential to offer a great avenue for future development and implementation in water treatment. It could lead to improved methods of treating water, which would be beneficial for both environmental protection and economic growth. The developed adsorbent had high adsorption affinity toward the THMs compounds, making the adsorption method efficient and viable technique for treating water containing such contaminants.

Ameliorative effect of montelukast against STZ induced diabetic nephropathy: targeting HMGB1, TLR4, NF-κB, NLRP3 inflammasome, and autophagy pathways - Ahmed M. Awad; Sally L. Elshaer; Rajashekhar Gangaraju; Rania R. Abdelaziz; Manar A. Nader (Inflammopharmacology, 2024)
Diabetic nephropathy (DN) is reported as one of the most serious microvascular diabetic complications and the trigger of end-stage renal disease (ESRD), underscoring the concern of any therapeutic intervention directed at ameliorating the development and progression of DN. The current study explored the renoprotective impact of montelukast (Mon) against streptozotocin (STZ)-induced DN in rats compared to a standard anti-hyperglycemic insulin (Ins) treatment. Diabetes was induced by a single dose of STZ (55 mg/kg). Diabetic rats were treated with Mon (10 and 20 mg/kg, oral gavage) for eight weeks. Mon administration for 8 weeks after induction of diabetes conferred significant dose-dependent renoprotection, independent of blood glucose levels (unlike Ins), as evidenced by the improvement in serum creatinine, and blood urea nitrogen (BUN), and ameliorated STZ-induced renal necrotic, inflammatory alterations, and renal fibrosis. Additionally, Mon treatment in diabetic rats significantly restored redox hemostasis as evidenced by malondialdehyde (MDA) and total antioxidant capacity (TAC) levels; significantly reduced the renal expression of high mobility group box (HMGB) 1, toll-like receptor (TLR) 4, nuclear factor kappa B (NF-κB) (in the nucleus), NOD-like receptor family pyrin domain containing (NLRP) 3, and interleukin (IL)-1β. Moreover, Mon administration ameliorated the dysregulation in autophagy as evidenced by p62 and microtubule-associated protein 1A/1B-light chain 3 (LC3)-II levels. In conclusion, the renoprotective effect of Mon is potentially associated with its modulatory effect on inflammatory cytokines, antioxidant properties, and autophagy. Graphical Abstract Renoprotective effect of montelukast and its underlying pathway: Hyperglycemia and advanced glycation end products (AGEs) stimulate the release of high mobility group box (HMGB) 1 from necrotic and inflammatory cells. HMGB1 is considered as one of the endogenous ligands of toll-like receptor (TLR) 4, and the interaction of HMGB1 with TLR4 results in a subsequent translocation of nuclear factor kappa B (NF-κB) from the cytoplasm into the nucleus inducing an inflammatory response. NF-κB is a key mediator of the priming signal responsible for the activation of NOD-like receptor family pyrin domain containing (NLRP) 3 inflammasome by stimulating the expression of both NLRP3 and pro- interleukin (IL)-1β, which is then converted to IL-1β by to mediate inflammation. NLRP3 can induce reactive oxygen species production, while autophagy inhibits AGEs and NLRP3 accumulation. Montelukast show an inhibitory effect on HMGB1, TLR4, NF-κB, NLRP3, and IL-1β and has autophagy stimulating characteristics indicating its potential renoprotective effect.

The puzzling etiologies of transient black discoloration in Nile Tilapia (Oreochromis niloticus) intensively cultured under RAS system - Alaa Eldin Eissa; Marwa M. Attia; Rabia A. El Zlitne; Ayad A. Magdy; Asmaa Edrees; Mahmoud S. Sharaf; Abeer E. Mahmoud; Awad A. Abdelbaky; Rehab R. Abd ElMaged; Elshaimaa Ismael; Rehab A. Qorany; Doaa F. El Moghazi; et al. (Aquaculture International, 2024)
The aim of this study is to identify the hidden etiologies of the black chromo-shifting transient phenomenon affecting Nile tilapia, Oreochromis niloticus , farmed in RAS-controlled ponds together with the assessment of the immunological reaction against the chronic irritating effects of the invasive agent. A total of 100 Nile Tilapia were collected from a private farm at Kafrelsheikh Province, located on the northern side of the Egyptian Nile Delta. The clinical history of the affected fish farm showed an unknown chromo-shifting phenomenon where tilapias were exhibiting severe black skin coloration, which gradually disappeared after removal from the tank’s water. A comprehensive gross examination of the collected fish; including parasitological examination of skin and gill scraps, was performed. Blood biochemical testing was performed on the infested blackish O. niloticus and control non-infested fish. The current study showed that the monogenean parasite, Gyrodactylus cichlidarum , was the abundant parasite detected in the infested fish leading to abnormal black discoloration of skin and disruption of the immune system represented by significant increase of cortisol levels, lysozyme activity and different liver enzymes compared to the control. Treatment trials have been applied with moderate degrees of success, where the monogenean count was sharply decreased, and the normal skin color was remarkably restored, at the end of day 14 post-treatment. A triple treatment plan was initiated through 7 days’ application of 0.7 g/m 3 copper sulfates pentahydrate preceded by 1.5 ml/m 3 hydrogen peroxide 40% solution for the same period. One day after the end of the initial treatment, a maintenance dosage of 0.095 ml/m 3 of glutaraldehyde (15%)/quaternary ammonium compounds (QACs) mixture was administered for 3 days. As a supportive/immune-stimulant regimen, a weekly dosage of vitamin C (0.45 g g/m 3 ) and Saccharomyces cerevisiae (0.45 g/m 3 ) was added into the tank’s water to improve the general fish health.

Doxycycline-Loaded Calcium Phosphate Nanoparticles with a Pectin Coat Can Ameliorate Lipopolysaccharide-Induced Neuroinflammation Via Enhancing AMPK - Suzan Awad AbdelGhany Morsy; Mona Hassan Fathelbab; Norhan S. El-Sayed; Salma E. El-Habashy; Rania G. Aly; Sahar A. Harby (Journal of Neuroimmune Pharmacology, 2024)
Neuroinflammation occurs in response to different injurious triggers to limit their hazardous effects. However, failure to stop this process can end in multiple neurological diseases. Doxycycline (DX) is a tetracycline, with potential antioxidant and anti-inflammatory properties. The current study tested the effects of free DX, DX-loaded calcium phosphate (DX@CaP), and pectin-coated DX@CaP (Pec/DX@CaP) nanoparticles on the lipopolysaccharide (LPS)-induced neuroinflammation in mice and to identify the role of adenosine monophosphate-activated protein kinase (AMPK) in this effect. The present study was conducted on 48 mice, divided into 6 groups, eight mice each. Group 1 (normal control), Group 2 (blank nanoparticles-treated), Group 3 (LPS (untreated)), Groups 4, 5, and 6 received LPS, then Group 4 received free DX, Group 5 received DX-loaded calcium phosphate nanoparticles (DX@CaP), and Group 6 received DX-loaded calcium phosphate nanoparticles with a pectin coat (Pec/DX@CaP). At the end of the experimentation period, behavioral tests were carried out. Then, mice were sacrificed, and brain tissue was extracted and used for histological examination, and assessment of interleukin-6 positive cells in different brain areas, in addition to biochemical measurement of SOD activity, TLR-4, AMPK and Nrf2. LPS can induce prominent neuroinflammation. Treatment with (Pec/DX@CaP) can reverse most behavioral, histopathological, and biochemical changes caused by LPS. The findings of the current study suggest that (Pec/DX@CaP) exerts a significant reverse of LPS-induced neuroinflammation by enhancing SOD activity, AMPK, and Nrf2 expression, in addition to suppression of TLR-4. Graphical Abstract

Exergy and energy analysis of a novel solar powered fog desalination system - Ahmed E. Abu El-Maaty; Mohamed M. Awad; Bilal A. Qureshi (Desalination, 2024)

Ecofriendly synthesis and nematicidal application of copper nanoparticles fabricated from Bacillus subtilis AM18, against root-knot nematode of cucumber - Ramadan M. El-Ashry; Maha M. Nader; Ashwag Shami; Manal A. Alduwish; Ahmed Ezzat Ahmed; Soha A. Alamoud; Aminah Allohibi; Fatimah S. Alqahtani; Amira M. Alghamdi; Alshaymaa I. Ahmed; Mokhles A. A. Hassan; Salonaz E. Awad; et al. (European Journal of Plant Pathology, 2024)

Evaluating the protective role of trimetazidine versus nano-trimetazidine in amelioration of bilateral renal ischemia/reperfusion induced neuro-degeneration: Implications of ERK1/2, JNK and Galectin-3 /NF-κB/TNF-α/HMGB-1 signaling - Fatma E. Hassan; Basma Emad Aboulhoda; Isra H. Ali; Heba M. Elwi; Lamiaa M. Matter; Hend Ahmed Abdallah; Mohamed Mansour Khalifa; Asmaa Selmy; Mansour A. Alghamdi; Suzan Awad Morsy; Basant A. Al Dreny (Tissue and Cell, 2023)

A multi-analytical approach to investigate DOM dynamics and alum dose control in enhanced coagulation process using wide-ranging surface waters - Hiua Daraei; Edoardo Bertone; John Awad; Rodney A. Stewart; Christopher W.K. Chow; Jinming Duan; John Van Leeuwen (Journal of Water Process Engineering, 2023)

WITHDRAWN: Integration of an O2 transport membrane and a biomass-fueled SCO2 cycle for liquid CO2/freshwater/power production: ANN-based optimization and techno-economic evaluation - Linfu Huo; Yu Jiang; Miao You; Yuqi Bo; Aliashim Albani; Awad A. Ibraheem; Tamim Alkhalifah; Salem Alkhalaf; Fahad Alturise (Journal of Cleaner Production, 2023)

Evaluating Mesh Geometry and Shade Coefficient for Fog Harvesting Collectors - Abdullah A. Elshennawy; Magdy Y. Abdelaal; Ahmed M. Hamed; Mohamed M. Awad (Water Resources Management, 2023)
The most valuable resource for sustaining life on earth is water. In dry and semi-arid areas, the problem of water scarcity can be resolved with the aid of fog collection techniques employing fog collectors. Fog collection is greatly influenced by a variety of factors. Some are design parameters, while others depend on ambient circumstances. Geometry and the mesh’s shade coefficient are important design factors that can be modified and have an impact on the rate at which fog collects in fog collectors. The shape of the mesh holes and the process used to create the mesh serve to identify geometry and measure the shade coefficient. In this paper, a straightforward mathematical technique is proposed to make it easier to calculate the shade coefficient of various mesh shapes used in fog harvesting and to provide an approximation of the mesh volume and cost. Five alternative geometries were used: the rectangular mesh, square mesh, Raschel mesh, triangular mesh, and hexagonal mesh. The current simple method will facilitate the design of the fog mesh collector and can assist in achieving the ideal shade coefficient and most effective mesh geometry for fog harvesting. Rectangular meshes were solely used as an example to evaluate the results. Stainless steel rectangular meshes with various shade coefficients were tested for fog collection, and the amount of water collected by each mesh varied. It was concluded that the optimum shade coefficient ranged 50–60% for fog collection.

Evaluating the effect of Spirulina platensis on the immune response of broiler chickens to various vaccines and virulent Newcastle disease virus challenge - Ashraf M. Awad; Mahmoud E. Sedeik; Ahmed H. Salaheldin; Raghda I. Goda; Nahed A. El-Shall (Research in Veterinary Science, 2023)

Tailoring surface topography of biochar-based hydrogel for hazardous pollutants removal from contaminated seawater through simultaneous steam-electricity generation - Rania Tarek; Doaa A. Kospa; S.A. El-Hakam; Awad I. Ahmed; Amr Awad Ibrahim (Desalination, 2023)

Growth patterns of Pseudomonas aeruginosa in milk fortified with chitosan and selenium nanoparticles during refrigerated storage - Rehab M. Atia; Hamdi A. Mohamed; Nahla A. AboELRoos; Dina A. B. Awad (World Journal of Microbiology and Biotechnology, 2023)
Pseudomonas spp are considered a common milk-associated psychotropic bacteria, leading to milk deterioration during storage; therefore, our study aimed to study the distribution of Pseudomonas aeruginosa in raw milk and its associated products then studying the growth behavior of P. aeruginosa in milk after employing chitosan nanoparticles (CsNPs 50, 25, and 15 mg/100ml) and selenium nanoparticles (SeNPs 0.5, 0.3 and 0.1 mg/100ml) as a trial to control the bacterial growth in milk during five days of cooling storage. Our study relies on the ion gelation method and green synthesis for the conversion of chitosan and selenium to nanosized particles respectively, we subsequently confirmed their shape using SEM and TEM. We employing Pseudomonas selective agar medium for monitoring the bacterial growth along the cooling storage. Our findings reported that high prevalence of Pseudomonas spp count in raw milk and kareish cheese and high incidence percent of P. aeruginosa in ice cream and yogurt respectively. Both synthesized nanoparticles exhibited antibacterial activity in a dose-dependent manner. Moreover, CsNPs50 could inhibit the P. aeruginosa survival growth to a mean average of 2.62 ± 1.18 log 10 cfu/ml in the fifth day of milk cooling storage; also, it was noted that the hexagonal particles SeNPs0.5 could inhibit 2.49 ± 11 log 10 cfu/ml in comparison to the control P. aeruginosa milk group exhibited growth survival rate 7.24 ± 2.57 log 10 cfu/ml under the same conditions. In conclusion, we suggest employing chitosan and selenium nanoparticles to improve milk safety and recommend future studies for the fate of nanoparticles in milk.

Prospects of resistance of some Sudanese tomato accessions to South American tomato pinworm, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) and its mechanism - Elharith H. Bakheit; Awad K. Taha; Mohammed E. E. Mahmoud; Telal S. Abdelhalim; Khitma A. S. Mustafa; El Tahir I. Mohamed; Eltayeb Abdellateef (International Journal of Tropical Insect Science, 2023)

Advances in catalytic dry reforming of methane (DRM): Emerging trends, current challenges, and future perspectives - Aliyu Musa Alhassan; Ijaz Hussain; Omer Ahmed Taialla; Mohammed Mosaad Awad; Abdulkadir Tanimu; Khalid Alhooshani; Saheed A. Ganiyu (Journal of Cleaner Production, 2023)

Synthesis, antiproliferative activity, and molecular modeling of novel 4-methylcoumarin derivatives and/or nitric oxide donor hybrids - Malik Suliman Mohamed; Hany A. M. Elsherief; Hani Mohamed Hafez; Omar Awad Alsaidan; Samil I. Alzarea; Asmaa M. AboulMagd (Molecular Diversity, 2023)

Neuromodulatory effect of vardenafil on aluminium chloride/d-galactose induced Alzheimer’s disease in rats: emphasis on amyloid-beta, p-tau, PI3K/Akt/p53 pathway, endoplasmic reticulum stress, and cellular senescence - Heba H. Awad; Mahmoud A. Desouky; Alaa Zidan; Mariam Bassem; Amaal Qasem; Mona Farouk; Haidy AlDeab; Miral Fouad; Cherry Hany; Nada Basem; Rita Nader; Ashrakat Alkalleny; et al. (Inflammopharmacology, 2023)
Dysregulation of protein homeostasis, proteostasis, is a distinctive hallmark of many neurodegenerative disorders and aging. Deleteriously, the accumulation of aberrant proteins in Alzheimer’s disease (AD) is accompanied with a marked collapse in proteostasis network. The current study explored the potential therapeutic effect of vardenafil (VAR), a phosphodiesterase-5 inhibitor, in AlCl 3 / d -galactose ( d -gal)-induced AD in rats and its possible underlying mechanisms. The impact of VAR treatment on neurobehavioral function, hippocampal tissue architecture, and the activity of the cholinergic system main enzymes were assessed utilizing VAR at doses of 0.3 mg/kg and 1 mg/kg. Additionally, the expression level of amyloid-beta and phosphorylated tau proteins in the hippocampus were figured out. Accordingly, VAR higher dose was selected to contemplate the possible underlying mechanisms. Intriguingly, VAR elevated the cyclic guanosine monophosphate level in the hippocampus and averted the repressed proteasome activity by AlCl 3 / d -gal; hence, VAR might alleviate the burden of toxic protein aggregates in AD. In addition, a substantial reduction in the activating transcription factor 6-mediated endoplasmic reticulum stress was demonstrated with VAR treatment. Notably, VAR counteracted the AlCl 3 / d -gal-induced depletion of nuclear factor erythroid 2-related factor 2 level. Moreover, the anti-senescence activity of VAR was demonstrated via its ability to restore the balance of the redox circuit. The modulation of phosphatidylinositol-3-kinase/protein kinase B/p53 pathway and the reduction of nuclear factor kappa B level, the key regulator of senescence-associated secretory phenotype mediators release, with VAR treatment were also elucidated. Altogether, these findings insinuate the possible therapeutic benefits of VAR in AD management. Graphic abstract

Alleviation of black root rot symptoms and alteration of strawberry growth via modulating physiological and biochemical mechanisms using Trichoderma viride and Bacillus subtilis - Mohamed A. E. Abied; Mohamed I. I. Khalil; Mohamed F. Awad; Sahar A. Youssef (European Journal of Plant Pathology, 2023)

Exploring the potential of quercetin/aspirin-loaded chitosan nanoparticles coated with Eudragit L100 in the treatment of induced-colorectal cancer in rats - Mohammed Elmowafy; Khaled Shalaby; Mohammed H. Elkomy; Omar Awad Alsaidan; Hesham A. M. Gomaa; Omnia M. Hendawy; Mohamed A. Abdelgawad; Hazim M. Ali; Yasmin M. Ahmed; Khalid M. El-Say (Drug Delivery and Translational Research, 2023)

Experimental and theoretical studies on nitrate removal using epichlorohydrin-modified cross-linked chitosan derived from shrimp waste - Rachid EL Kaim Billah; Hassane Lgaz; Daniel Goma Jiménez; Preeti Pal; Balter Trujillo-Navarrete; Mohammadi Ahrouch; Jari S. Algethami; Youness Abdellaoui; Hicham Majdoubi; Awad A. Alrashdi; Mahfoud Agunaou; Abdessadik Soufiane; et al. (Environmental Science and Pollution Research, 2023)

Effects of dietary nano-selenium supplementation on Riemerella anatipestifer vaccinated and challenged Pekin ducklings (Anas platyrhynchos) - Abdelfattah H. Eladl; Nehal M. Nabil; Amal Awad; Shereen Badr; Amera F. Ebrahem; Maram M. Tawakol; Enas Hammad; Hanaa S. Ali; Reham A. El-Shafei (Veterinary Microbiology, 2023)

Effect of potential microplastics in sewage effluent on Nile Tilapia and photocatalytic remediation with zinc oxide nanoparticles - Manal Qayyadh Alanazi; Promy Virk; Seham Soliman Alterary; Manal Awad; Zubair Ahmad; Abdulrehman M. Albadri; KalidM. Ortashi; Mohieldeen Mahgoub A. Ahmed; Mohamed Ismail Ali Yousef; Mai Elobeid; Ebtesam Abdullah Al-Qahtani (Environmental Pollution, 2023)

Phytochemical analysis and determination of antioxidant, anti-cholesterol, anti-inflammatory and anti-proliferative activities of Gerbera jamesonii flowers - Shaimaa Negm El-Dein; Amal Hussein; Marwa S. Abu-Bakr; Asmaa Negm El-Dein; Hanem M. Awad; Ehab A. Ragab (Advances in Traditional Medicine, 2023)

DOC signal-based alum dose control for drinking water treatment plants - Hiua Daraei; John Awad; Edoardo Bertone; Rodney A. Stewart; Christopher W.K. Chow; Jinming Duan; Jonathan Creamer; John Van Leeuwen (Journal of Water Process Engineering, 2023)

The Middle-Upper Eocene benthic foraminifera from north-west Fayoum area, Egypt: Paleoecology and their similarity to the Tethyan provinces - Sherif M. El Baz; Hamdalla A. Wanas; Heba Allah Abou Awad; Ehab M. Assal (Journal of African Earth Sciences, 2023)

Circulating Plasma miRNA Homologs in Mice and Humans Reflect Familial Cerebral Cavernous Malformation Disease - Sharbel G. Romanos; Abhinav Srinath; Ying Li; Bingqing Xie; Chang Chen; Yan Li; Thomas Moore; Dehua Bi; Je Yeong Sone; Rhonda Lightle; Nick Hobson; Dongdong Zhang; et al. (Translational Stroke Research, 2023)

Correction to: Dephenolization and discoloration of olive mill wastewater using coagulation, filtration, and hydrogen peroxide oxidation - M. A. Al-Shaweesh; A. Awad; D. Al-Kabariti; M. S. Al-Hwaiti; Omar A. Al-Khashman; A. F. Khafaga; M. E. Abd El-Hack; F. A. Adday (International Journal of Environmental Science and Technology, 2023)

Dephenolization and discoloration of olive mill wastewater using coagulation, filtration, and hydrogen peroxide oxidation - M. A. Al-Shaweesh; A. Awad; D. Al-Kabariti; M. S. Al-Hwaiti; O. A. Al-Kashman; A. F. Khafaga; M. E. Abd El-Hack; F. A. Adday (International Journal of Environmental Science and Technology, 2023)

Geotechnical Properties of Clay Soil Contaminated with Different Types of Oil - Zuheir Karabash; Moataz A. Al-Obaydi; Muwafaq A. Awad; Mohamed N. Al-Khashab (Geotechnical and Geological Engineering, 2023)

Corrigendum to “Prasugrel anti-ischemic effect in rats: Modulation of hippocampal SUMO2/3-IкBα/Ubc9 and SIRT-1/miR-22 trajectories” [Toxicol Appl Pharmacol. 2021 Sep 1;426:115635] - Asmaa A. Gomaa; Hanan S. El-Abhar; Dalaal M. Abdallah; Azza S. Awad; Ayman A. Soubh (Toxicology and Applied Pharmacology, 2023)

Experimental investigation of solar still productivity enhancement of distilled water by using natural fibers - AbedAlrzaq Alshqirate; Ahmad S. Awad; Aiman Al Alawin; Mohamed A. Essa (Desalination, 2023)

Novel control of house fly Musca domestica and bacterial isolates by ozone gas - Ahmed M. Metwally; Salem S. Salem; Kotb M. Hammad; Khaled H. Metwaly; Mohamed A. Awad (International Journal of Tropical Insect Science, 2023)
Ozone is a sturdy oxidant which canrub insects and microorganisms. Thus, it could be useful in eliminate the Housefly in hospitals. The purpose of test here is to determine degree of ozone exposure required to remove houseflies and reduction of pathogenic bacteria. Ozone was effective with housefly, requiring only low minutes of treatment (1 to 14 min.) at minimum concentrations of ozone gas O 3 (0.125 g/m 3 to 1 g/m 3 ), the insects were eliminated the ozone. Thus, ozone exhibit potential as a fumigant for ousefly nesting materials, but moreover research is needed to evaluate its acceptability and efficacy in that field. The need for a dependable method to decontaminate housefly nesting materials as part of an overall ousefly ( Musca domestica ) system at hospitals sterilization is discussed. In this paper, we are using ozone gas as an alternative housefly pest and to remove house flies at hospitals, and we also illustrate data on the efficacy of ozone against the housefly ( Musca domestica ) and its effect on specific characteristics and properties of the treated zone application is currently attracting attention, particularly since. (a) There are no residues on the product. (b) There is no need for aeration to remove the gas. Green synthesis industrial applications and improvements in ozone technology together with new regulatory actions worldwide have emerged in last years, making it easier to use and applicable in a wide range - as the same with the pathogenic bacteria we are using ozone gas to control it, the numbers of bacterial cells remaining after ozone treatments were less than for untreated cells. The lowest dose of ozone gas for complete reduction of pathogenic bacteria was 0.125 g/m 3 after 24 h of incubation.

Fe-Co spinel oxides supported UiO-66-NH2 derived zirconia/ N-dopped porous hollow carbon as an efficient oxygen reduction reaction electrocatalyst - Soliman Gamal; Doaa A. Kospa; Mahmoud M. Kaid; S.A. El-Hakam; Awad I. Ahmed; Amr Awad Ibrahim (Journal of Environmental Chemical Engineering, 2023)

Suppression of Meloiodogyne incognita (Tylenchida: Heteroderidae) and Tylenchulus semipenterans (Tylenchida: Tylenchulidae) using Tilapia fish powder and plant growth promoting rhizobacteria in vivo and in vitro - Ramadan M. El-Ashry; Ahmed A. A. Aioub; Salonaz E. Awad (European Journal of Plant Pathology, 2023)
Plant-parasitic nematodes (PPNs) in particular those belonging to the genera Meloidogyne and Tylenchulus are a limiting factor in the production of many plants. In this research, we investigate a strategy for the control of PPNs in vivo and in vitro. The purpose of this research is to evaluate different concentrations of Tilapia fish powder (TFP) and of (in the form of BECTO Grow Roots®) against egg hatching and second-stage juveniles of Meloiodogyne incognita (Tylenchida: Heteroderidae) under laboratory condition. We also assessed the effect of TFP and on M. incognita and Tylenchulus semipenterans (Tylenchida: Tylenchulidae) reproduction. Our data showed that the percentage of egg hatching inhibition ranged from 8.03 to 53.21% and 42.25 to 75.12% after five days of treatment at different concentrations of TFP and PGPR, respectively compared with the control. The percentage of M. incognita J2 mortality increase significantly ( p ≤ 0.05) from 52.1 to 86.7 and 44.6 to 92.3% after seven days of treatment at different concentrations of TFP and PGPR, respectively compared with control. Under greenhouse conditions, a remarkable ( p ≤ 0.05) increase in plant growth parameters was observed in cucumber plants that received TFP and In the field experiment, the highest reduction of T. semipeneterans density was TFP + PGPR This holds both for healthy and infected trees. Healthy navel orange (HNO) + PGPR + TFP achieved maximum enhancement in orange weight/tree compared to other treatments. Our study recommended TFP and PGPR not only because of their potential against nematodes, but also because of their safety for humans, mammals and non-target organisms.

Hydrophilic candle wastes microcapsules as a thermal energy storage material for all-day steam and electricity cogeneration - Yasmine Adel Younes; Doaa A. Kospa; Reda S. Salama; Awad I. Ahmed; Amr Awad Ibrahim (Desalination, 2023)

Carbohydrate microcapsules tailored and grafted for covalent immobilization of glucose isomerase for pharmaceutical and food industries - Mohamed E. Hassan; Ghada E. A. Awad; Mohamed S. MohyEldin; Bakry M. Haroun; Ahmed I. El-Diwany; Magdy M. Elnashar (Biotechnology Letters, 2023)

Sensitivity of the grooved carpet shell clam, Ruditapes decussatus (Linnaeus, 1758), to ocean acidification - Merna E. Awad; Fedekar F. Madkour; Nayrah A. Shaltout; Mohamed Abu El-Regal; Ahmed Elshazly; Eman El-Wazzan (Arabian Journal of Geosciences, 2023)

Hypouricemic, anti-inflammatory, and antioxidant activities of Lactobacillus-based functional yogurt in induced-arthritic male Wistar rats: Therapeutic and protective potentials - Asmaa Negm El-Dein; Asmaa Ezzat; Hanan Farouk Aly; Eman A. Younis; Ghada A. Awad; Mohamed A.M. Farid (Biocatalysis and Agricultural Biotechnology, 2023)

Influence of COVID-19 on the sustainability of livestock performance and welfare on a global scale - Md. Tanvir Rahman; Md. Saiful Islam; Awad A. Shehata; Shereen Basiouni; Hafez M. Hafez; Esam I. Azhar; Asmaa F. Khafaga; Fulvia Bovera; Youssef A. Attia (Tropical Animal Health and Production, 2022)

Eco-friendly and regiospecific intramolecular cyclization reactions of cyano and carbonyl groups in N,N-disubstituted cyanamide - Amr H. Moustafa; Walaa W. Ahmed; Mohamed F. Awad; Moustafa O. Aboelez; Ahmed Khodairy; Amer A. Amer (Molecular Diversity, 2022)

The diagnostic accuracy of intraoperative frozen section biopsy for diagnosis of sentinel lymph node metastasis in breast cancer patients: a meta-analysis - Alaa Ahmed Elshanbary; Alaa Abdelsameia Awad; Alaa Abdelsalam; Islam H. Ibrahim; Walid Abdel-Aziz; Youssef Bahaaeldin Darwish; Alaa Saad Isa; Boutheyna Drid; Marwa Gamal Mustafa; Radwa Hamdy Allam; Amira A. Abo Ali; Anas Zakarya Nourelden; et al. (Environmental Science and Pollution Research, 2022)
Sentinel lymph node (SLN) sampling is important for evaluating the nodal stage of breast cancer when the axillary nodes are clinically free of metastasis. The intraoperative frozen section (IFS) of SLN is used for lymph node assessment. This meta-analysis aims to provide evidence about the diagnostic accuracy and the applicability of IFS of SLN in breast cancer patients. Data were collected by searching PubMed, Cochrane, Scopus, and Web of Science electronic databases for trials matching our eligibility criteria. The statistical analysis included the sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and pooled studies’ diagnostic odds ratio outcomes. The analyses were conducted using the Open Meta-analyst software. This meta-analysis pooled the results of 110 studies. The overall sensitivity of IFS for SLN metastasis was 74.7%; 95% CI [72.0, 77.2], P < 0.001. It was 31.4% 95% CI [25.2, 38.3], P < 0.001 for the micro-metastasis, and 90.2%; 95% CI [86.5, 93.0], P < 0.001 for the macro-metastasis. The overall specificity was 99.4%; 95% CI [99.2, 99.6], P < 0.001. The overall positive likelihood ratio was 121.4; 95% CI [87.9, 167.6], P < 0.001, and the overall negative likelihood ratio was 0.226; 95% CI [0.186, 0.274], P < 0.001. The overall diagnostic odds ratio of IFS for diagnosing SLN metastasis was 569.5; 95% CI [404.2, 802.4], P < 0.001. The intraoperative frozen section of SLN has good sensitivity for diagnosing breast cancer macro-metastasis. However, the sensitivity is low for micro-metastasis. The specificity is very satisfactory.

Anticancer activity of chicken cathelicidin peptides against different types of cancer - Maged Mostafa Mahmoud; Modhi Alenezi; Ahmed M. Al-Hejin; Turki S. Abujamel; Fadwa Aljoud; Abdulwahab Noorwali; Ibrahim A. Awad; Mohammed Alkhaled; Haitham A. Yacoub (Molecular Biology Reports, 2022)

Solar photo-oxidation of recalcitrant industrial wastewater: a review - Ahmed Tawfik; Mohamed Gar Alalm; Hanem M. Awad; Muhammad Islam; Muhammad Abdul Qyyum; Ala’a H. Al-Muhtaseb; Ahmed I. Osman; Moonyong Lee (Environmental Chemistry Letters, 2022)
Conventional methods to clean wastewater actually lead to incomplete treatments, calling for advanced technologies to degrade recalcitrant pollutants. Herein we review solar photo-oxidation to degrade the recalcitrant contaminants in industrial wastewater, with focus on photocatalysts, reactor design and the photo-Fenton process. We discuss limitations due to low visible-light absorption, catalyst collection and reusability, and production of toxic by-products. Photodegradation of refractory organics by solar light is controlled by pH, photocatalyst composition and bandgap, pollutant properties and concentration, irradiation type and intensity, catalyst loading, and the water matrix.

Occupational ocular health problems among marble workers at Shaq El Tho’ban industrial area in Egypt - Enjy A. E. Khorshed; Safaa A. El-Naggar; Samia S. El-Gohary; Ahmed M. B. Awad; Amani S. Ahmed (Environmental Science and Pollution Research, 2022)
Eye health of the working population is an essential condition for productivity. Marble industry is processed at large scale at Shaq El Tho’ban area where much dust, crushed pieces of stone, and fluctuating temperatures are endangering employees’ health generally and eye health specifically. The objectives of this study were assessing the prevalence of the most common ocular health problems associated with marble industry and investigating the impact of the working environment and occupational risk factors on the oculo-visual status of marble workers. A cross-sectional study was conducted among 250 workers, working at Shaq El Tho’ban area in Egypt during the period from August 2020 to September 2021, using a semi-structured questionnaire and eye examination comprised of full ocular history, visual acuity testing (unaided/aided), slit lamp examination, ophthalmoscopy, and Schirmer’s type I and tear break up time tests. The current study showed that gritty sensation (65.2%) and eye dryness (51.2%) were the commonest symptoms complained. By examination, conjunctival hyperemia (59.6%) was the most prevalent finding. By performing dry eye tests, dry eye was diagnosed in 60.4% and 51.2% of workers by Schirmer’s test and tear break up time test respectively. The study’s results indicated that age, working category, smoking, and diabetes had significant impact on development of ocular symptoms, while working duration, diabetes, smoking, ocular symptoms, and ocular foreign body had significant impact on development of dry eye disease. Implementation of engineering control measures, proper designing, and supply of eye PPE together with adequate health education to all workers about occupational health risks and preventive measures are recommended.

Effect of Gryllotalpa gryllotalpa (Orthoptera: Gryllotalpidae) on plant and crop characteristics of sugar beet, Beta vulgaris L. and detection of associated damage using hyperspectral remote sensing - Amira H. A. Moursey; Mohamed Aboelghar; Magda Khattab; Mona Awad; Ibtisam A. Hemeida; Sayeda S. Ahmed (International Journal of Tropical Insect Science, 2022)

Integrated Effect of Filter Mud Cake Combined with Chemical and Biofertilizers to Enhance Potato Growth and Its Yield - Ahmed M. Ali; Sabry A. Hegab; Assem M. Abd El Gawad; Mahrous Awad (Journal of Soil Science and Plant Nutrition, 2022)

Enhancement of photocatalytic and biological activities of chitosan/activated carbon incorporated with TiO2 nanoparticles - Medhat E. Owda; Ahmed S. Elfeky; Ragab E. Abouzeid; Ahmed K. Saleh; Mohamed A. Awad; Haitham A. Abdellatif; Fakher M. Ahmed; Ahmed S. Elzaref (Environmental Science and Pollution Research, 2022)

Verification of pull-out resistance of anchors in soil/rock formations using empirical and finite element methods - A. H. Abdel-Rahman; M. F. Awad-Allah (Innovative Infrastructure Solutions, 2022)

Therapeutic effect of dithiophenolato chitosan nanocomposites against carbon tetrachloride-induced hepatotoxicity in rats - Nadia Z. Shaban; Ahmed M. Aboelsaad; Doaa Awad; Shaymaa A. Abdulmalek; Shaban Y. Shaban (Environmental Science and Pollution Research, 2022)

Oxidative stress, apoptosis and histopathological alterations in brain stem and diencephalon induced by subacute exposure to fipronil in albino rats - Mohamed A. Awad; Zainab Sabry Othman Ahmed; Huda O. AbuBakr; Gehad Abd El-Fattah Hassan Elbargeesy; Moukhtar H. G. Moussa (Environmental Science and Pollution Research, 2022)

Vulnerability of tourism to climate change on the Mediterranean coastal area of El Hammam–EL Alamein, Egypt - Esraa A. El-Masry; Mahmoud Kh. El-Sayed; Mohamed A. Awad; Amr A. El-Sammak; Mohamed A. El Sabarouti (Environment, Development and Sustainability, 2022)

Carbonated ground granulated blast furnace slag stabilising brown kaolin - Ahmed Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Ahmad Safuan A. Rashid; Suksun Horpibulsuk (Environmental Science and Pollution Research, 2021)

Promising bioadhesive ofloxacin-loaded polymeric nanoparticles for the treatment of ocular inflammation: formulation and in vivo evaluation - Alaa H. Salama; Mona M. AbouSamra; Ghada E. A. Awad; Soheir S. Mansy (Drug Delivery and Translational Research, 2021)

An acetylated derivative of vitexin halts MDA-MB-231 cellular progression and improves its immunogenic profile through tuning miR- 20a-MICA/B axis - Aya R. Awad; Rana A. Youness; M. Ibrahim; Amira Abdel Motaal; Hesham I. El-Askary; Reem.A. Assal; Mohamed Z. Gad (Natural Product Research, 2021)

Using statistical approaches in permeability prediction in highly heterogeneous carbonate reservoirs - Faisal Awad Aljuboori; Jang Hyun Lee; Khaled A. Elraies; Karl D. Stephen (Carbonates and Evaporites, 2021)

Evolutionary insights into the furin cleavage sites of SARS-CoV-2 variants from humans and animals - Abdou Nagy; Shereen Basiouni; Rokshana Parvin; Hafez M. Hafez; Awad A. Shehata (Archives of Virology, 2021)

3D Deep Neural Network Segmentation of Intracerebral Hemorrhage: Development and Validation for Clinical Trials - Matthew F. Sharrock; W. Andrew Mould; Hasan Ali; Meghan Hildreth; Issam A. Awad; Daniel F. Hanley; John Muschelli (Neuroinformatics, 2021)

Biochemical and microbiological characteristics of some Mediterranean salted fish products - Adel A. A. Mohdaly; Awad A. Mahmoud; Mohamed Fawzy Ramadan; Mohamed H. H. Roby (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Embryonic thermal manipulation of Japanese quail: effects on embryonic development, hatchability, and post-hatch performance - Saad N. El-Shater; Hamdy Rizk; Hisham A. Abdelrahman; Mohamed A. Awad; Elsayed F. Khalifa; Karim M. Khalil (Tropical Animal Health and Production, 2021)

Molecular docking studies, in-silico ADMET predictions and synthesis of novel PEGA-nucleosides as antimicrobial agents targeting class B1 metallo-β-lactamases - Jesica A. Mendoza; Richard Y. Pineda; Michelle Nguyen; Marisol Tellez; Ahmed M. Awad (In Silico Pharmacology, 2021)

Correction to: Ground improvement and its role in carbon dioxide reduction: a review - Ahmed Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Dayang Zulaika Abang Hasbollah; Ahmad Safuan A Rashid (Environmental Science and Pollution Research, 2021)

The impact of diagenesis precipitation on fracture permeability in naturally fractured carbonate reservoirs - Faisal Awad Aljuboori; Jang Hyun Lee; Khaled A. Elraies; Karl D. Stephen (Carbonates and Evaporites, 2021)

Ground improvement and its role in carbon dioxide reduction: a review - Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Dayang Zulaika Abang Hasbollah; Ahmad Safuan A Rashid (Environmental Science and Pollution Research, 2021)

Integrated remote sensing and GIS for developed new spectral index for estimating Sandy land and its potential hazards. Case study: north-east Al-Muthanna Province area, south of Iraq - Awad A. Sahar; Abdulkhaleq A. Alhadithi; Mustafa Ali Hassan; Ammar A. Jasim (Arabian Journal of Geosciences, 2021)

Synoptic features associated with the winter variability of the subtropical jet stream over Africa and the Middle East - Mana A. Asiri; Mansour Almazroui; Adel M. Awad (Meteorology and Atmospheric Physics, 2020)

Nano-diagnostic technique for detection of rice pathogenic fungus Pyricularia oryzae - Ibrahim H. El-Abbasi; Amal A. Khalil; Hossam M. Awad; Tahsin Shoala (Indian Phytopathology, 2020)

Molecular characterization of pathogenic Escherichia coli isolated from diarrheic and in-contact cattle and buffalo calves - Walid S. Awad; Amr A. El-Sayed; Faten F. Mohammed; Noha M. Bakry; Nadra-Elwgoud M. I. Abdou; Mohamed S. Kamel (Tropical Animal Health and Production, 2020)

Graviola leaves extract enhances the anticancer effect of cisplatin on various cancer cell lines - Mai G. Awad; Ramadan A. Ali; Dalia D. Abd El-Monem; Mohammed A. El-Magd (Molecular & Cellular Toxicology, 2020)

Novel Murine Models of Cerebral Cavernous Malformations - Matthew R. Detter; Robert Shenkar; Christian R. Benavides; Catherine A. Neilson; Thomas Moore; Rhonda Lightle; Nicholas Hobson; Le Shen; Ying Cao; Romuald Girard; Dongdong Zhang; Erin Griffin; et al. (Angiogenesis, 2020)

Common transcriptome, plasma molecules, and imaging signatures in the aging brain and a Mendelian neurovascular disease, cerebral cavernous malformation - Janne Koskimäki; Sean P. Polster; Yan Li; Sharbel Romanos; Abhinav Srinath; Dongdong Zhang; Julián Carrión-Penagos; Rhonda Lightle; Thomas Moore; Seán B. Lyne; Agnieszka Stadnik; Kristina Piedad; et al. (GeroScience, 2020)

Formulation and Evaluation of Novel Hybridized Nanovesicles for Enhancing Buccal Delivery of Ciclopirox Olamine - Mona M. AbouSamra; Alaa H. Salama; Ghada E. A. Awad; Soheir S. Mansy (AAPS PharmSciTech, 2020)

Effect of a Dietary Mixture of Beneficial Bacteria on Growth Performance, Health Condition, Chemical Composition, and Water Quality of Nile Tilapia, Oreochromis niloticus Fingerlings - Malik M. Khalafalla; Safinaz A. Ibrahim; Mohamed M. Zayed; Mohamed N. Awad; Radi A. Mohamed (Journal of Aquatic Food Product Technology, 2020)

Effects of the Probiotic Candidate E. faecalis-1, the Poulvac E. coli Vaccine, and their Combination on Growth Performance, Caecal Microbial Composition, Immune Response, and Protection against E. coli O78 Challenge in Broiler Chickens - Reda Tarabees; Mohamed S. El-Sayed; Awad A. Shehata; Mohamed S. Diab (Probiotics and Antimicrobial Proteins, 2020)

Effect of fracture characteristics on history matching in the Qamchuqa reservoir: a case study from Iraq - Faisal Awad Aljuboori; Jang Hyun Lee; Khaled A. Elraies; Karl D. Stephen (Carbonates and Evaporites, 2020)

Repurposing of Secukinumab as Neuroprotective in Cuprizone-Induced Multiple Sclerosis Experimental Model via Inhibition of Oxidative, Inflammatory, and Neurodegenerative Signaling - Amany El-Shahawy Abdel-Maged; Amany M. Gad; Laila Ahmed Rashed; Samar S. Azab; Eman A. Mohamed; Azza S. Awad (Molecular Neurobiology, 2020)

A Brain-Targeted Orally Available ROCK2 Inhibitor Benefits Mild and Aggressive Cavernous Angioma Disease - Lisa McKerracher; Robert Shenkar; Matthew Abbinanti; Ying Cao; Amy Peiper; James K. Liao; Rhonda Lightle; Thomas Moore; Nicholas Hobson; Carol Gallione; Joerg Ruschel; Janne Koskimäki; et al. (Translational Stroke Research, 2020)

Correction to: Indoor air fungal pollution of a historical museum, Egypt: a case study - Abdel Hameed A. Awad; Yuosra Saeed; Alia A. Shakour; Nasser M. Abdellatif; Yasser H. Ibrahim; Manal Elghanam; Fatma Elwakeel (Aerobiologia, 2020)

Indoor air fungal pollution of a historical museum, Egypt: a case study - Abdel Hameed A. Awad; Yuosra Saeed; Alia A. Shakour; Nasser M. Abdellatif; Yasser H. Ibrahim; Manal Elghanam; Fatma Elwakeel (Aerobiologia, 2020)

Inhibition of the Prostaglandin EP-1 Receptor in Periosteum Progenitor Cells Enhances Osteoblast Differentiation and Fracture Repair - Marina Feigenson; Jennifer H. Jonason; Jie Shen; Alayna E. Loiselle; Hani A. Awad; Regis J. O’Keefe (Annals of Biomedical Engineering, 2020)

A chemosensoring molecular lab for various analytes and its ability to execute a molecular logical digital comparator - Awad I. Said; Nikolai I. Georgiev; Shaimaa A. Hamdan; Vladimir B. Bojinov (Journal of Fluorescence, 2019)

Neutron activation and ICP-MS analyses of metals in dust samples—Kingdom of Saudi Arabia: concentrations, pollution, and exposure - Atef El-Taher; Wael M. Badawy; B. Alshahrani; Awad A. Ibraheem (Arabian Journal of Geosciences, 2019)

Effects of Dietary Supplementation of Probiotic Mix and Prebiotic on Growth Performance, Cecal Microbiota Composition, and Protection Against Escherichia coli O78 in Broiler Chickens - Reda Tarabees; Khaled M. Gafar; Mohamed S. EL-Sayed; Awad A. Shehata; Marwa Ahmed (Probiotics and Antimicrobial Proteins, 2019)

Optimum salinity for Nile tilapia (Oreochromis niloticus) growth and mRNA transcripts of ion-regulation, inflammatory, stress- and immune-related genes - Ahmed A. A. El-Leithy; Shaaban A. Hemeda; Walaa S. H. Abd El Naby; Abeer F. El Nahas; Seham A. H. Hassan; Simone T. Awad; Safaa I. El-Deeb; Zeinab A. Helmy (Fish Physiology and Biochemistry, 2019)

Feeding of deoxynivalenol increases the intestinal paracellular permeability of broiler chickens - Wageha A. Awad; Daniel Ruhnau; Claudia Hess; Barbara Doupovec; Dian Schatzmayr; Michael Hess (Archives of Toxicology, 2019)

Endophytic actinomycetes Streptomyces spp mediated biosynthesis of copper oxide nanoparticles as a promising tool for biotechnological applications - Saad El-Din Hassan; Amr Fouda; Ahmed A. Radwan; Salem S. Salem; Mohammed G. Barghoth; Mohamed A. Awad; Abdullah M. Abdo; Mamdouh S. El-Gamal (JBIC Journal of Biological Inorganic Chemistry, 2019)

The Utilization of Electric Arc Furance Slag in Soil Improvement - A. I. M. Ismail; S. A. Awad; M. A. G. Mwafy (Geotechnical and Geological Engineering, 2019)

Empagliflozin, SGLT2 inhibitor, attenuates renal fibrosis in rats exposed to unilateral ureteric obstruction: potential role of klotho expression - Noha A. T. Abbas; Amal El. Salem; Mohammed M. Awad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Exertional heat illness: knowledge and behavior among construction workers - Dalia A. El-Shafei; Sarah A. Bolbol; Marwa B. Awad Allah; Amira E. Abdelsalam (Environmental Science and Pollution Research, 2018)

Association between exposure to pesticides and disorder on hematological parameters and kidney function in male agricultural workers - Nagah M. Hassanin; Osama M. Awad; Sourya El-Fiki; Reda A. I. Abou-Shanab; Ahmed R. A. Abou-Shanab; Ranya A. Amer (Environmental Science and Pollution Research, 2018)

Formulation and characterization of garlic (Allium sativum L.) essential oil nanoemulsion and its acaricidal activity on eriophyid olive mites (Acari: Eriophyidae) - Abdel-Tawab H. Mossa; Sahar I. Afia; Samia M. M. Mohafrash; Badawi A. Abou-Awad (Environmental Science and Pollution Research, 2018)

Flavones from Heavenly Blue as modulators of Alzheimer’s amyloid-beta peptide (Aβ) production - Hanem M. Awad; Howaida I. Abd-Alla; Mohamed A. Ibrahim; Eslam R. El-Sawy; Mohamed M. Abdalla (Medicinal Chemistry Research, 2018)

Synthesis and in vitro antitumor evaluation of novel Schiff bases - Ashraf S. Hassan; Hanem M. Awad; Asmaa A. Magd-El-Din; Taghrid S. Hafez (Medicinal Chemistry Research, 2018)

The use of connectivity clusters in stochastic modelling of highly heterogeneous porous media - Mohamed A. Awad; Ahmed E. Hassan; Hesham M. Bekhit (Arabian Journal of Geosciences, 2018)

Plasma Biomarkers of Inflammation Reflect Seizures and Hemorrhagic Activity of Cerebral Cavernous Malformations - Romuald Girard; Hussein A. Zeineddine; Maged D. Fam; Anoop Mayampurath; Ying Cao; Changbin Shi; Robert Shenkar; Sean P. Polster; Michael Jesselson; Ryan Duggan; Abdul-Ghani Mikati; Gregory Christoforidis; et al. (Translational Stroke Research, 2018)

Molecular characterization of very virulent infectious bursal disease virus strains circulating in Egypt from 2003 to 2014 - Awad A. Shehata; Hesham Sultan; Mohammed Y. Halami; Shaimaa Talaat; Thomas W. Vahlenkamp (Archives of Virology, 2017)

Neuroprotective Effects of Simvastatin and Cilostazol in l-Methionine-Induced Vascular Dementia in Rats - Ahmed M. El-Dessouki; Mai A. Galal; Azza S. Awad; Hala F. Zaki (Molecular Neurobiology, 2017)

Cytotoxic activity evaluation and molecular docking study of phenolic derivatives from Achillea fragrantissima (Forssk.) growing in Egypt - Basma M. Awad; Eman S. Habib; Amany K. Ibrahim; Amira S. Wanas; Mohamed M. Radwan; Mohamed A. Helal; Mahmoud A. ElSohly; Safwat A. Ahmed (Medicinal Chemistry Research, 2017)

Phenotypic and Genotypic Characterization of Bacteriocinogenic Enterococci Against Clostridium botulinum - Awad A Shehata; Reda Tarabees; Shereen Basiouni; Mahmoud Gamil; Ahmed S Kamal; Monika Krüger (Probiotics and Antimicrobial Proteins, 2017)

Impact of thyme powder (Thymus vulgaris L.) supplementation on gene expression profiles of cytokines and economic efficiency of broiler diets - Fardos A. M. Hassan; Ashraf Awad (Environmental Science and Pollution Research, 2017)

Possible correlation between levansucrase production and probiotic activity of Bacillus sp. isolated from honey and honey bee - Abdelhamid A. Hamdy; Nouran A. Elattal; Magdy A. Amin; Amal E. Ali; Nahla M. Mansour; Ghada E. A. Awad; Hassan M. Awad; Mona A. Esawy (World Journal of Microbiology and Biotechnology, 2017)

Efficacy of cold fogging and oral herbal extracts on air quality and immune response of broilers - Awad A. Shehata; Klaus Herrmann; Thomas Pfalz; Hafez M. Hafez; Wieland Schrödl; Monika Krüger (Aerobiologia, 2017)

3D Printing of Calcium Phosphate Ceramics for Bone Tissue Engineering and Drug Delivery - Ryan Trombetta; Jason A. Inzana; Edward M. Schwarz; Stephen L. Kates; Hani A. Awad (Annals of Biomedical Engineering, 2017)

Effect of Water Regimes and Palm Coefficient on Growth Parameters, Date Yield and Irrigation Water Use of Tissue Culture‐Regenerated ‘Barhee’ Date Palms Grown in a Newly Established Orchard - Adel D. Al‐Qurashi; Saleh M. Ismail; Mohamed A. Awad (Irrigation and Drainage, 2016)
A field experiment was carried out at the Agriculture Experimental Station of King Abdulaziz University during the 2013 and 2014 seasons to study the effect of water regimes and palm coefficient on growth parameters, yield and irrigation water use (IWU) of tissue culture‐derived ‘Barhee’ date palm cultivars in a newly established orchard. Four water regimes T1, T2, T3 and T4 representing 70, 85, 100 and 115% of water requirement were studied to select the best water regime that maximizes yield and IWU. Water requirement in 2013 was calculated based on the FAO palm coefficient ( K p ) but based on measured K p during 2014. Results revealed that using measured K p reduces water requirements in the summer season and increases date yield. It saves about 12% of irrigation water compared to FAO K p . Increasing the water regime increased yield per palm, where the highest yield was obtained from T4 (16.5 kg per tree), and the least from T1(12.4 kg per tree). IWU is increased by decreasing the water regime. However, the differences between T4 and T3 were not significant, indicating that giving the highest water regime produces the highest yield. It is concluded that increasing water supply maximizes yield production of young tissue culture‐derived ‘Barhee’ date palms in a newly established orchard. Copyright © 2016 John Wiley & Sons, Ltd.

Two new proanthocyanidin trimers isolated from Cistus incanus L. demonstrate potent anti-inflammatory activity and selectivity to cyclooxygenase isoenzymes inhibition - K. A. Mansoor; K. Z. Matalka; F. S. Qa’dan; R. Awad; M. Schmidt (Natural Product Research, 2016)

Anticancer activity of some [1,2,4]triazepino[2,3-a] quinazoline derivatives: monolayer and multicellular spheroids in vitro models - Hanem M. Awad; Walid Fayad; Salwa M. El-Hallouty; Thoraya A. Farghaly; Mohamad M. Abdallah (Medicinal Chemistry Research, 2016)

B-Cell Depletion Reduces the Maturation of Cerebral Cavernous Malformations in Murine Models - Changbin Shi; Robert Shenkar; Hussein A. Zeineddine; Romuald Girard; Maged D. Fam; Cecilia Austin; Thomas Moore; Rhonda Lightle; Lingjiao Zhang; Meijing Wu; Ying Cao; Murat Gunel; et al. (Journal of Neuroimmune Pharmacology, 2016)

Thymoquinone alleviates nonalcoholic fatty liver disease in rats via suppression of oxidative stress, inflammation, apoptosis - Azza S. M. Awad; Ekram N. Abd Al Haleem; Wesam M. El-Bakly; Mohie A. Sherief (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Source mechanism and parameters of the 19 October 2012 earthquake, northern Egyptian continental margin - Awad Hassoup; Mostafa Toni; M. M. F. Shokry; A. M. A. Helal; Emad K. Mohamed (Arabian Journal of Geosciences, 2016)

Curcumin Ameliorates Lead (Pb2+)-Induced Hemato-Biochemical Alterations and Renal Oxidative Damage in a Rat Model - Ashraf M. Abdel-Moneim; Mona Y. El-Toweissy; Awatef M. Ali; Abd Allah M. Awad Allah; Hanaa S. Darwish; Ismail A. Sadek (Biological Trace Element Research, 2015)

Detection of Clostridium botulinum in liquid manure and biogas plant wastes - Jürgen Neuhaus; Wieland Schrödl; Awad A. Shehata; Monika Krüger (Folia Microbiologica, 2015)

Isolation and full genome characterization of avian influenza subtype H9N2 from poultry respiratory disease outbreak in Egypt - Awad A. Shehata; Rokshana Parvin; Hesham Sultan; Mohamed Y. Halami; Shaimaa Talaat; Alaa Abd Elrazek; Mahmoud Ibrahim; Kristin Heenemann; Thomas Vahlenkamp (Virus Genes, 2015)

The feed contaminant deoxynivalenol affects the intestinal barrier permeability through inhibition of protein synthesis - Wageha A. Awad; Jürgen Zentek (Archives of Toxicology, 2015)

Tomato treatment with chemical inducers reduces the performance of Spodoptera littoralis (Lepidoptera: Noctuidae) - Islam S. Sobhy; Nasser S. Mandour; Awad A. Sarhan (Applied Entomology and Zoology, 2015)

A climatological study: wet season cyclone tracks in the East Mediterranean region - Mansour Almazroui; Adel M. Awad; M. Nazrul Islam; A. K. Al-Khalaf (Theoretical and Applied Climatology, 2015)

The Influence of Glyphosate on the Microbiota and Production of Botulinum Neurotoxin During Ruminal Fermentation - Wagis Ackermann; Manfred Coenen; Wieland Schrödl; Awad A. Shehata; Monika Krüger (Current Microbiology, 2015)

Detection of pathogenic clostridia in biogas plant wastes - Jürgen Neuhaus; Awad A. Shehata; Monika Krüger (Folia Microbiologica, 2015)

Possible Effects of Glyphosate on Mucorales Abundance in the Rumen of Dairy Cows in Germany - Wieland Schrödl; Susanne Krüger; Theodora Konstantinova-Müller; Awad A. Shehata; Ramon Rulff; Monika Krüger (Current Microbiology, 2014)

Characterization of a genetic and antigenic variant of avian paramyxovirus 6 isolated from a migratory wild bird, the red-necked stint (Calidris ruficollis) - Vuong Nghia Bui; Tetsuya Mizutani; Tung Hoang Nguyen; Dai Quang Trinh; Sanaa S. A. Awad; Germaine L. Minoungou; Yu Yamamoto; Kikuyasu Nakamura; Keisuke Saito; Yukiko Watanabe; Jonathan Runstadler; Falk Huettmann; et al. (Archives of Virology, 2014)

In vitro anti-nitrosative, antioxidant, and cytotoxicity activities of plant flavonoids: a comparative study - Hanem M. Awad; Howaida I. Abd-Alla; Khaled H. Mahmoud; Sayed A. El-Toumy (Medicinal Chemistry Research, 2014)

An evidence for the transcriptional regulation of iodothyronine deiodinase 2 by progesterone in ovarectomized rats - Hossam A. Awad; Zienab A. Alrefaie (Journal of Physiology and Biochemistry, 2014)

Log-derived petrophysical characteristics and oil potentiality of the Upper Qishn Clastic Member, Masila Basin, Yemen - Awad A. Omran; Nabil M. Alareeq (Arabian Journal of Geosciences, 2014)

Life history traits of Blaptostethus pallescens (Hemiptera: Anthocoridae), a candidate for use in augmentative biological control in Egypt - Islam S. Sobhy; Amany M. Abdul-Hamid; Awad A. Sarhan; Ahmed A. Shoukry; Nasser S. Mandour; Stuart R. Reitz (Applied Entomology and Zoology, 2014)

Life history of Proprioseiopsis badri feeding on four eriophyid mite species (Acari: Phytoseiidae and Eriophyidae) - Faten M. Momen; Abd-Elsatar M. Metwally; Abd Elrady K. Nasr; Awad A. Abdallah; Khaled M. Saleh (Phytoparasitica, 2014)

OPTIMIZATION OF IRRIGATION WATER USE, YIELD, AND QUALITY OF 'NABBUT‐SAIF' DATE PALM UNDER DRY LAND CONDITIONS - Saleh M. Ismail; Adel D. Al‐Qurashi; Mohamed A. Awad (Irrigation and Drainage, 2014)
A field experiment was conducted in the western part of Saudi Arabia to optimize irrigation water use (IWU), yields and quality of the 'Nabbut‐Saif' date palm grown in sandy loam soil under arid conditions. Four water regimes were investigated. The supplied amounts of irrigation water were 50, 65, 82 and 100% of date palm water requirements to the first (W1), second (W2), third (W3) and fourth (W4) water regimes, respectively. The daily water requirement was calculated using the Penman–Montieth equation for dry climates and applied to the trees three times a week through a drip irrigation system. Results indicated that giving 65% of total date palm water requirement maximized date yield by producing 46.1 kg per tree and resulted in the best IWU (0.8 m 3 kg −1 per tree). Increasing the water regime to 82 and 100% of total water requirement produced only 45.5 and 46 kg per tree respectively and reduced IWU. Generally, fruit quality characteristics were insignificantly affected by the water regimes investigated. The results suggested that supplying 34 m 3 yr −1 per tree for date palms grown under the conditions of the western part of Saudi Arabia is enough to maximize IWU, yield and quality of the 'Nabbut‐Saif' date palm cultivar. Copyright © 2014 John Wiley & Sons, Ltd.

Chicken embryo origin-like strains are responsible for Infectious laryngotracheitis virus outbreaks in Egyptian cross-bred broiler chickens - Awad A. Shehata; Mohammad Y. Halami; Hesham H. Sultan; Alaa G. Abd El-Razik; Thomas W. Vahlenkamp (Virus Genes, 2013)

The Effect of Glyphosate on Potential Pathogens and Beneficial Members of Poultry Microbiota In Vitro - Awad A. Shehata; Wieland Schrödl; Alaa. A. Aldin; Hafez M. Hafez; Monika Krüger (Current Microbiology, 2013)

Exploration of copper deposits in Wadi El Regeita area, Southern Sinai, Egypt, with contribution of remote sensing and geophysical data - S. M. Salem; Sultan Awad Arafa; T. M. Ramadan; El Sayed A. El Gammal (Arabian Journal of Geosciences, 2013)

Regional Heterogeneity of Cuprizone-Induced Demyelination: Topographical Aspects of the Midline of the Corpus Callosum - T. Schmidt; H. Awad; A. Slowik; C. Beyer; M. Kipp; T. Clarner (Journal of Molecular Neuroscience, 2013)

Lateral variations of coda Q and attenuation of seismic waves in the Gulf of Suez, Egypt - Mamdouh A. Morsy; Sherif El Hady; Salah M. Mahmoud; Enayat Abdel Moneim Awad (Arabian Journal of Geosciences, 2013)

Palynozonation of the Cretaceous to Lower Paleogene strata of the Muglad Basin, Sudan - Ali A.M. Eisawi; Awad B. Ibrahim; Omer Babiker A. Rahim; Eckart Schrank (Palynology, 2012)

Association study between the dopamine-related candidate gene polymorphisms and ADHD among Saudi Arabia population via PCR technique - Adel E. El-Tarras; Adnan A. Alsulaimani; Nabil S. Awad; Nahla Mitwaly; Manal M. Said; Ayman M. Sabry (Molecular Biology Reports, 2012)

Effect of some pyrimidine compounds on rat brain monoamine oxidase-B in vitro - Nadia Z. Shaban; Mamdouh S. Masoud; Mai A. Mawlawi; Doaa Awad; Omayma M. Sadek (Journal of Physiology and Biochemistry, 2012)

Anti-HIV-1 and cytotoxicity of the alkaloids of Erythrina abyssinica Lam. growing in Sudan - Magdy M.D. Mohammed; Nabaweya A. Ibrahim; Nagwa E. Awad; Azza A. Matloub; Ahmed G. Mohamed-Ali; Ezzieldeen E. Barakat; Ahmed E. Mohamed; Paolo L. Colla (Natural Product Research, 2012)

Efficacy of Ficus spp. on renal injury induced by hypercholesterolaemia - Nagwa E. Awad; Manal A. Hamed; Ahmed A. Seida; Marwa M. Elbatanony (Natural Product Research, 2012)

Synthesis, antimicrobial, antioxidant, anti-inflammatory, and analgesic activities of some new 3-(2′-thienyl)pyrazole-based heterocycles - Bakr F. Abdel-Wahab; Hassan Abdel-Gawad; Ghada E. A. Awad; Farid A. Badria (Medicinal Chemistry Research, 2012)

Phytochemical and in vitro screening of some Ficus and Morus spp. for hypolipidaemic and antioxidant activities and in vivo assessment of Ficus mysorensis (Roth) - Nagwa E. Awad; Ahmed A. Seida; Manal A. Hamed; Ahlam H. Mahmoud; Marwa M. Elbatanony (Natural Product Research, 2012)

Fluorescence and Electrochemical Recognition of Nucleosides and DNA by A Novel Luminescent Bioprobe Eu(lll) -TNB - Hassan A. Azab; E. M. Mogahed; F. K. Awad; R. M. Abd El Aal; Rasha M. Kamel (Journal of Fluorescence, 2012)

Less is More: Treatment with BTH and Laminarin Reduces Herbivore-Induced Volatile Emissions in Maize but Increases Parasitoid Attraction - Islam S. Sobhy; Matthias Erb; Awad A. Sarhan; Monir M. El-Husseini; Nasser S. Mandour; Ted C. J. Turlings (Journal of Chemical Ecology, 2012)

Fluorescence and Electrochemical Sensing of Pesticides Methomyl, Aldicarb and Prometryne by the Luminescent Europium-3-Carboxycoumarin Probe - Hassan A. Azab; Axel Duerkop; E. M. Mogahed; F. K. Awad; R. M. Abd El Aal; Rasha M. Kamel (Journal of Fluorescence, 2012)

Endogenous tissue engineering: PTH therapy for skeletal repair - Masahiko Takahata; Hani A. Awad; Regis J. O’Keefe; Susan V. Bukata; Edward M. Schwarz (Cell and Tissue Research, 2012)

Impact of DNA repair genes polymorphism (XPD and XRCC1) on the risk of breast cancer in Egyptian female patients - Yousry Mostafa Hussien; Amal F. Gharib; Hanan A. Awad; Rehab A. Karam; Wael H. Elsawy (Molecular Biology Reports, 2012)

Evaluation of shear strength of cohesionless soil due to excess pore water pressure - Awad A. Al-Karni (Arabian Journal of Geosciences, 2011)

Climatology and classification of Spring Saharan cyclone tracks - A. Hannachi; A. Awad; K. Ammar (Climate Dynamics, 2011)

Integrated geophysical interpretation for the area located at the eastern part of Ismailia Canal, Greater Cairo, Egypt - Sultan Awad Sultan; Fernando A. M. Santos; Ahmad Sobhy Helaly (Arabian Journal of Geosciences, 2011)

Hypolipidaemic and antioxidant activities of Ficus microcarpa (L.) in hypercholesterolemic rats - Nagwa E. Awad; Ahmed A. Seida; Manal A. Hamed; Marwa M. Elbatanony (Natural Product Research, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Development, consumption rates and reproductive biology of Orius albidipennis reared on various prey - Islam S. Sobhy; Awad A. Sarhan; Ahmed A. Shoukry; Gamal A. El-Kady; Nasser S. Mandour; Stuart R. Reitz (BioControl, 2010)

Air biocontamination in a variety of agricultural industry environments in Egypt: a pilot study - Abdel Hameed A. Awad; Tarek H. Elmorsy; Patrick M. Tarwater; Christopher F. Green; Shawn G. Gibbs (Aerobiologia, 2010)

Decontamination and detoxification strategies for the Fusarium mycotoxin deoxynivalenol in animal feed and the effectiveness of microbial biodegradation - Wageha A. Awad; Khaled Ghareeb; Josef Böhm; Jürgen Zentek (Food Additives & Contaminants: Part A, 2010)

Preparation of Intravenous Stealthy Acyclovir Nanoparticles with Increased Mean Residence Time - Amany O. Kamel; Gehanne A. S. Awad; Ahmed S. Geneidi; Nahed D. Mortada (AAPS PharmSciTech, 2009)

New acylated flavone and cyanogenic glycosides from Linum grandiflorum - Magdy M.D. Mohammed; Lars P. Christensen; Nabaweya A. Ibrahim; Nagwa E. Awad; Ibrahim F. Zeid; Erik B. Pedersen (Natural Product Research, 2009)

Multicomponent image segmentation: a comparative analysis between a hybrid genetic algorithm and self‐organizing maps - M. M. Awad; K. Chehdi; A. Nasri (International Journal of Remote Sensing, 2009)

Release Mechanisms Behind Polysaccharides-Based Famotidine Controlled Release Matrix Tablets - Enas M. Elmowafy; Gehanne A. S. Awad; Samar Mansour; Abd El-Hamid A. El-Shamy (AAPS PharmSciTech, 2008)

Do camels (Camelus dromedarius) play an epidemiological role in the spread of Shiga Toxin producing Escherichia coli (STEC) infection? - A. El-Sayed; S. Ahmed; W. Awad (Tropical Animal Health and Production, 2008)

2-D and 3-D resistivity in the area of the Menkaure Pyramid Giza, Egypt - Abbas Mohamed Abbas; Sultan Awad Sultan; Fernando A. Monteiro Santos (Bulletin of Engineering Geology and the Environment, 2008)

Mechanisms of Enhancing Photosynthetic Gas Exchange in Date Palm Seedlings (Phoenix dactylifera L.) under Salinity Stress by a 5-Aminolevulinic Acid-based Fertilizer - Tarek Youssef; Mohamed A. Awad (Journal of Plant Growth Regulation, 2008)

Activity-directed-fractionation and isolation of four antibacterial compounds from Abrus precatorius L., roots - G. B. Zore; V. Awad; A. D. Thakre; U. K. Halde; N. S. Meshram; B. S. Surwase; S. Mohan Karuppayil (Natural Product Research, 2007)

Levo-tetrahydropalmatine attenuates cocaine self-administration and cocaine-induced reinstatement in rats - John R. Mantsch; Shi-Jiang Li; Robert Risinger; Sarah Awad; Eric Katz; David A. Baker; Zheng Yang (Psychopharmacology, 2007)

Airborne dust, bacteria, actinomycetes and fungi at a flourmill - Abdel Hameed A. Awad (Aerobiologia, 2007)

Self-medication practices in Khartoum State, Sudan - Abdelmoneim Ismail Awad; Idris Babiker Eltayeb; Phillip A. Capps (European Journal of Clinical Pharmacology, 2006)

Changing antibiotics prescribing practices in health centers of Khartoum State, Sudan - A. I. Awad; I. B. Eltayeb; O. Z. Baraka (European Journal of Clinical Pharmacology, 2006)

Vegetation: A source of air fungal bio-contaminant - Abdel Hameed A. Awad (Aerobiologia, 2005)

In vitro propagation and cryostorage of Syzygium francissi (Myrtaceae) by the encapsulation-dehydration method - M. Awad Shatnawi; Krystyna A. Johnson; Fraser R. Torpy (In Vitro Cellular & Developmental Biology - Plant, 2004)

Blastocystis hominis as a cause of hypoalbuminemia and anasarca - E. Nassir; J. Awad; A. B. Abel; J. Khoury; M. Shay; F. Lejbkowicz (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Neuroleptic dysphoria: towards a new synthesis - L. Voruganti; A. G. Awad (Psychopharmacology, 2004)

Modulation of mitogen-independent hepatocyte proliferation during the perinatal period in the rat - Philip A. Gruppuso; Michael Awad; Theresa C. Bienieki; Joan M. Boylan; Shaneli Fernando; Ronald A. Faris (In Vitro Cellular & Developmental Biology - Animal, 1997)

Biological studies ofAmblyseius olivi, a new predator of eriophyid mites infesting olive trees in Egypt [Acari: Phytoseiidae] - B. A. Abou-Awad; E. M. El-Banhawy (BioControl, 1986)

Effect of synthetic pyrethroids and other compounds on the susceptibility and development of the egg stage of the predacious miteAmblyseius gossipi [Mesostigmata: Phytoseiidae] - E. M. El-Banhawy; B. A. Abou-Awad (BioControl, 1985)

Amblyseius gossipi [Acarina: Phytoseiidae] as a predator of the tomato erineum mite,Eriophyes lycopersici [Acarina: Eriophyidae] - Badawi A. Abou-Awad (BioControl, 1983)